Filling and bonding material, filling and bonding material with protective sheet, laminate, optical device, and protective panel for optical device
By designing filling bonding materials with unequal thickness shapes, the problem of filling gaps in curved optical devices with thin film sheet adhesives has been solved, achieving efficient seamless filling and improved mechanical strength, as well as enhanced visual recognition and durability.
Patent Information
- Application Number
- CN202411308786.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2017-05-18
- Filing Date
- 2018-01-16
- Publication Date
- 2025-01-10
AI Technical Summary
Existing thin-film acrylic adhesives are prone to introducing air bubbles during the bonding process, which reduces visual clarity and durability. They are particularly difficult to fill gaps in curved optical devices and fail to meet display performance requirements.
Using filler materials of varying thicknesses and shapes, the design is matched according to the shape of the gaps between components. Materials such as polyvinyl acetal are used, and the coating method of the liquid bonding agent and the hot pressing conditions are adjusted to ensure seamless filling and mechanical strength.
It enables seamless filling in optical devices of various shapes, maintaining display performance and mechanical strength, avoiding bubble residue, and improving visual recognition and durability.
Smart Images

Figure CN119286407A_ABST
Abstract
Description
[0001] This application is a divisional application. The filing date of the parent application is January 16, 2018. The international application number is PCT / JP2018 / 001045. The application number entering the Chinese national phase is 201880003107.8. The name of the invention is filling bonding material, filling bonding material with protective sheet, laminate, optical device and protective panel for optical device. Technical Field
[0002] The present invention relates to a filling bonding material that can be suitably used for filling between components while laminating components in optical devices having various shapes not limited to flat surfaces, etc. In addition, the present invention relates to a filling bonding material with a protective sheet, a laminate, an optical device, and a protective panel for an optical device containing the filling bonding material. Background Art
[0003] Transparent adhesive sheets and the like are known for bonding components and filling the gaps between the components. For example, acrylic adhesives are widely used for filling the gaps between display modules, touch panel modules, and surface protection panels including glass, etc. (e.g., Patent Document 1). In such devices, the gaps between components are filled with transparent adhesive sheets and the like having a small refractive index difference with the components, thereby improving optical quality (transparency, brightness, contrast, etc.) and visual recognition.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2011-74308 Summary of the invention
[0007] Problems to be solved by the invention
[0008] However, conventional film-sheet-shaped acrylic adhesives may sometimes trap bubbles during lamination, and bubbles may remain between the surface protection panel and the acrylic adhesive, which may reduce visual recognition or durability. In addition, a printed portion is sometimes formed on the back side of the surface protection panel at the peripheral portion for the purpose of shielding, etc., and there is a concern that bubbles may remain at the height difference formed by such a printed portion or at the boundary of the height difference of the electrical wiring, thereby reducing visual recognition or durability.
[0009] In addition, in recent years, with the diversification of optical devices, optical devices with various shapes not limited to flat surfaces have been continuously appearing for the purpose of improving design, and optical devices or display devices with curved surfaces have also been proposed. It is believed that such devices are formed by bonding a display module, a touch panel module and a curved surface protection panel, but the conventional film-like acrylic adhesive cannot fill the gap, so they cannot be directly bonded. In addition, a gap of, for example, 1 mm to several cm is assumed according to the product design, but such a thick film acrylic adhesive is difficult to produce.
[0010] Furthermore, especially in touch panels, if the touched area is misaligned with the corresponding display content, problems may arise in the operation and movement of the device. As can be seen, if there is a curved interface with a refractive index difference, it is difficult for conventional film-like acrylic adhesives to achieve the same display performance as in the case of a flat surface.
[0011] The object of the present invention is to provide a filling bonding material that can be suitably used for filling between components while laminating the components in optical devices having various shapes not limited to flat surfaces, etc. In addition, the object of the present invention is to provide a filling bonding material with a protective sheet, a laminate, an optical device, and a protective panel for an optical device containing the filling bonding material.
[0012] Solution to the problem
[0013] The present invention is a filling and bonding material with a shape of unequal thickness. The present invention is described in detail below.
[0014] The inventors of the present invention have found that by forming the filling bonding material into a shape with unequal thickness, that is, a shape matching the shape of the gap between the components to be bonded, it can be suitably used to fill the gap between the components while bonding the components in optical devices having various shapes not limited to a plane. By using such a filling bonding material, even optical devices having various shapes not limited to a plane can satisfy the same display performance and mechanical strength as those of a planar optical device.
[0015] In this specification, the filling bonding material refers to a material that can bond adherends to each other without an adhesive or pressure-sensitive adhesive at the interface with the adherends and can fill the space (gap) between the adherends.
[0016] The filling and bonding material of the present invention has a shape with uneven thickness.
[0017] Thus, the filling bonding material of the present invention can be suitably used for filling between components while laminating components in optical devices having various shapes not limited to planes, etc. By using the filling bonding material of the present invention, even optical devices having various shapes not limited to planes, etc. can satisfy the same display performance and mechanical strength as those of planar optical devices.
[0018] In this specification, the term "unequal thickness shape" refers to a shape other than a rectangle (cuboid), for example, a shape with different thicknesses or a shape with a bias in thickness, etc. However, even a shape that deforms into an unequal thickness shape when a force is applied, such as a flat plate-like shape with a uniform thickness when left at room temperature, such as a general film or adhesive sheet, is not included.
[0019] The filling bonding material of the present invention preferably has a curved surface.
[0020] As the above-mentioned curved surface, more specifically, for example, convex curved surfaces and concave curved surfaces can be cited. In addition, the above-mentioned curved surface can constitute a part of the surface of the filling bonding material, or it can constitute the whole. It should be noted that the filling bonding material of the present invention can have a fine structure on the surface, but the unequal thickness shape referred to in the present invention does not include the fine structure of the surface itself. That is, a filling bonding material with a smooth plane on a macro scale can have a microscopic shape (for example, a surface roughness of several nm to several 10μm), and these shapes are not included in the unequal thickness shape.
[0021] The filling bonding material of the present invention preferably has a principal curvature of 1 / 5000 mm. -1 Here, the principal curvature refers to the maximum value of the normal curvature. It should be noted that, when the radius of curvature is set to R, the curvature of the surface is represented by 1 / R. The more preferred lower limit of the principal curvature is 1 / 2000 mm. -1 , and the further preferred lower limit is 1 / 1000mm -1 .
[0022] The arc length of the curved surface is preferably 50 mm or more. Here, the arc length of the curved surface refers to the length of a curve formed by the intersection of the curved surface and the normal plane that gives the curved surface its principal curvature (maximum value of normal curvature) (also called normal section).
[0023] The chord length of the curved surface is preferably 50 mm or more. Here, the chord length of the curved surface refers to the distance between the end points of the normal cross section.
[0024] It should be noted that Fig.17 A schematic diagram illustrating the arc length and chord length of a surface.
[0025] The above-mentioned curved surface preferably has a positive or negative Gaussian curvature. That is, it is preferred that the Gaussian curvature is not 0 (zero). It should be noted that the Gaussian curvature refers to the product of the maximum value of the normal curvature and the minimum value of the normal curvature. Such a curved surface does not have a direction where the curvature is 0 (zero). If it is a filling bonding material with such a curved surface, a more complex curved surface can be formed, so it can be applied to optical devices with various shapes that are not limited to planes, and can provide an optical device that is excellent in design while satisfying the same display performance and mechanical strength as the case of a plane optical device.
[0026] As the shape of the filling bonding material of the present invention, specifically, for example, prisms, cylinders, semi-cylinders and other cylindrical shapes, pyramids, cones and other conical shapes, truncated pyramids, truncated cones and other truncated cone shapes, spheres, hemispheres, ellipses and other shapes, and combinations thereof can be cited. These shapes may have openings or through holes in a portion. As the shape having a through hole, for example, a hollow cylindrical shape can be cited.
[0027] The shape of the filling bonding material of the present invention can be suitably designed and processed according to the shape of the bonding member (adherend). In addition, the shape of the filling bonding material of the present invention can be suitably designed and processed in a manner that follows the height difference of the decorative printing part (the height difference of the printing part on the back side of the surface protection panel), the height difference of the wiring (the height difference of the wiring formed on the touch panel), the height difference between the frame provided at the periphery of the touch panel module and the display module and the touch panel surface and the display surface, etc.
[0028] In addition, it is also possible to form a shape of unequal thickness by forming it into several parts (blocks) separately and finally joining them. The method of joining the blocks to form a shape of unequal thickness is not particularly limited, but it is preferred to apply a liquid bonding agent to each block, or to apply heat and pressure to each block while the liquid bonding agent is impregnated and maintained for a certain period of time. By such a method, it is possible to suppress the situation where bubbles remain between the blocks, and even large or complex shapes of unequal thickness can be seamlessly and easily formed. In addition, by adjusting the coating method of the liquid bonding agent, the conditions of heat and pressure, it is also possible to temporarily fix the blocks.
[0029] The liquid bonding aid preferably contains a liquid plasticizer. The liquid bonding aid is not particularly limited, and examples thereof include a plasticizer used together with the polyvinyl acetal described below, an alcohol (e.g., ethanol), a reactive diluent, water, and the like. Two or more of these liquid bonding aids may be mixed and used. The liquid bonding aid may contain a polyvinyl acetal resin, a photopolymerization initiator, an adhesive aid (e.g., a silane coupling agent), and the like.
[0030] The preferred lower limit of the maximum value (t1) of the thickness of the filling and bonding material of the present invention is 300 μm. If the maximum value (t1) of the thickness is 300 μm or more, even if the adherend is difficult to fill and bond with a conventional film sheet adhesive, the gap can be filled and bonded. The more preferred lower limit of the maximum value (t1) of the thickness is 500 μm, and the further preferred lower limit is 1000 μm.
[0031] It should be noted that the thickness of the filling bonding material refers to the length in the direction perpendicular to the bonding surface of a pair of bonding members (adherents) bonded by the filling bonding material. In the case of a complex surface shape, the length in the optical axis direction (the main direction of light emission or light reception) of the optical device can be set as the thickness to determine the maximum value of the thickness (t1).
[0032] The preferred lower limit of the difference between the maximum thickness (t1) and the minimum thickness (t2) of the filling bonding material of the present invention is 100 μm. If the difference is 100 μm or more, a relatively large curved surface shape can be filled. The more preferred lower limit of the difference is 300 μm.
[0033] The preferred lower limit of the maximum value of the width of the filling bonding material of the present invention is 50 mm, and the more preferred lower limit is 100 mm.
[0034] It should be noted that the width of the filling bonding material refers to the length in the direction perpendicular to the thickness of the filling bonding material.
[0035] The filling bonding material of the present invention preferably has at least one plane. By being constituted in this way, a display module or a touch panel module of a conventional shape that is usually in a plane shape can be used as an adherend. Among them, the filling bonding material of the present invention preferably has a plane and a curved surface (which can be convex or concave) relative to the above-mentioned plane. Such a shape can also be referred to as a convex or concave lens shape. By being set to such a shape, the filling bonding material, for example, in an optical device with a curved surface shape, is suitable for being used for filling these components while laminating a display module or a touch panel module of a usually flat shape with a curved surface protection panel, and can provide a panel with excellent design and operability during manufacturing.
[0036] The filling bonding material of the present invention preferably has a light-transmitting portion. Through the light-transmitting portion, light incident on the bonded member (adherend) can be guided to the outside of the filling bonding material, or incident light from the outside can be obtained. The bonded member (adherend) and the filling bonding material are preferably bonded in the light-transmitting portion, but can also be bonded in an area outside the light-transmitting portion. That is, the filling bonding material of the present invention can have a main bonding surface and a secondary bonding surface. By configuring in this way, the bonded member (adherend) and the filling bonding material can be bonded even outside the light-transmitting portion, so even if the bonded member (adherend) is a complex shape, filling and bonding between the members can be performed without damaging the optical quality. The main bonding surface and the secondary bonding surface may be continuous or discontinuous with each other. In addition, the main bonding surface and the secondary bonding surface may be on the same plane or the same curved surface. The filling bonding material of the present invention may have a plurality of main bonding surfaces and a plurality of secondary bonding surfaces, respectively.
[0037] Figure 1 This is a diagram schematically showing an example of the filling bonding material of the present invention and an example of its use form.
[0038] Figure 1 The filling bonding material 1 of the present invention shown in (a) has a flat surface and a convex curved surface (convex lens shape) opposite to the flat surface. Figure 1 As shown in (b), the filling bonding material 1 of the present invention can fill the gap between the flat touch panel module 2 and the curved surface protection panel 3 while bonding the two components. The touch panel module 2 and the surface protection panel 3 are a pair of bonded components (adherents), and the gap between the bonded components is filled with the filling bonding material 1 to form a laminate.
[0039] Figure 2 This is a diagram schematically showing an example of the filling bonding material of the present invention and an example of its use form.
[0040] Figure 2 The filling bonding material 1 of the present invention shown in (a) has a flat surface and a concave curved surface (concave lens shape) opposite to the flat surface. Figure 2 As shown in (b), the filling bonding material 1 of the present invention can fill the gap between the flat touch panel module 2 and the curved surface protection panel 3 while bonding the two components. The touch panel module 2 and the surface protection panel 3 are a pair of bonded components (adherents), and the gap between the bonded components is filled with the filling bonding material 1 to form a laminate.
[0041] Figure 3 This is a perspective view schematically showing an example of the filling bonding material of the present invention.
[0042] Figure 3The filling bonding material 1 of the present invention shown in (a) is a truncated pyramid (truncated quadrangular pyramid), Figure 3 The filling bonding material 1 of the present invention shown in (b) is a hemisphere (ellipse), Figure 3 The filling bonding material 1 of the present invention shown in (c) has a shape in which curved surfaces face each other. Figure 3 In (c), the curvatures of the relative curved surfaces may be the same or different.
[0043] Figure 4 The following are a perspective view and a cross-sectional view schematically showing an example of the filling bonding material of the present invention.
[0044] Figure 4 The filling bonding material 1 of the present invention shown in (a) (stereoscopic view) and (b) (cross-sectional view) is in a hollow cylindrical shape and has a cavity 4. In the cavity 4, for example, a component constituting an optical device can be inserted according to the product design (the component is covered with the filling bonding material of the present invention).
[0045] Figure 5 This is a cross-sectional view schematically showing an example of the filling bonding material of the present invention and an example of its use form.
[0046] like Figure 5 As shown, the filling bonding material 1 of the present invention can fill the gap between the flat touch panel module 2 and the curved surface protection panel 3 while bonding these components. In addition, the filling bonding material 1 of the present invention can fill the gap inside the frame 21 set at the peripheral portion of the touch panel module 2 while following the height difference.
[0047] The material of the filling bonding material of the present invention is not particularly limited, and can be adjusted, for example, in the following manner: by being in a solid or gel state at room temperature, it can maintain a shape of unequal thickness at room temperature. As the material of the filling bonding material of the present invention, for example, a thermoplastic resin, a cured product of a thermosetting resin, a cured product of a photocurable resin, and a mixture thereof can be used. Among them, a thermoplastic resin is preferably used.
[0048] Examples of the thermoplastic resin include polyvinyl acetal, ethylene-vinyl acetate copolymer, acid-modified olefin, (meth)acrylic copolymer, etc., and examples of the thermosetting resin include silicone resin, urethane resin, etc. Among them, the filling bonding material of the present invention preferably contains polyvinyl acetal at least on the surface.
[0049] In the case of using the conventional film-like acrylic adhesive, even if the thick film adhesive is to be shaped or processed into a shape of unequal thickness, it is difficult to shape or process it. In contrast, by using polyvinyl acetal, the shaping or processing into a shape of unequal thickness becomes easy, and the bonding to the adherend can be achieved. In the case of using polyvinyl acetal, a filling bonding material with excellent height difference tracking (anti-foaming) and anti-scattering (the performance of preventing fragments from scattering when optical devices, etc. are damaged) can be made. In addition, unlike the so-called adhesive such as the conventional film-like acrylic adhesive, there is less pollution to the adherend, and the reprocessability of the filling bonding material can also be achieved. Therefore, in the case of expensive adherends (for example, the adherend is a surface protection panel containing a large curved glass, a touch panel module, and an expensive display module), it is particularly advantageous in terms of cost. The filling bonding material of the present invention is made to contain polyvinyl acetal at least on the surface, and heat and pressure are applied and maintained for a certain period of time in a state of being stacked with the adherend, so that the adherend can be firmly bonded.
[0050] The polyvinyl acetal may be a plasticized polyvinyl acetal or a polyvinyl acetal not containing a plasticizer. Among them, the plasticized polyvinyl acetal is preferred. In the present specification, the plasticized polyvinyl acetal refers to a resin containing a polyvinyl acetal and a plasticizer.
[0051] The polyvinyl acetal can be prepared, for example, by saponifying polyvinyl acetate to obtain polyvinyl alcohol, and then acetalizing the obtained polyvinyl alcohol with an aldehyde in the presence of a catalyst. The saponification degree of the polyvinyl alcohol is not particularly limited, but is generally in the range of 70 to 99.9 mol %, preferably 70 to 99.8 mol %, more preferably 80 to 99.8 mol %.
[0052] The average degree of polymerization of the polyvinyl alcohol is not particularly limited, but from the viewpoint of obtaining more excellent anti-scattering property and reprocessing property, polyvinyl alcohol acetal with a large molecular weight is suitable, so it is preferred to use polyvinyl alcohol with a high average degree of polymerization. The preferred lower limit of the average degree of polymerization of the polyvinyl alcohol is 100, and the preferred upper limit is 4000. When the average degree of polymerization is 100 or more, the reprocessing property of the filling bonding material can be improved. In addition, from the viewpoint of mechanical strength, it is preferred that the average degree of polymerization is 200 or more. When the average degree of polymerization is 200 or more, the mechanical strength and anti-scattering property of the polyvinyl alcohol acetal can be prevented from being reduced. If the average degree of polymerization is 4000 or less, when the polyvinyl alcohol is acetalized, the solution viscosity will not increase abnormally, and the acetalization and the forming of the filling bonding material can be properly carried out. The more preferred lower limit of the average degree of polymerization is 600, the more preferred upper limit is 3800, the further preferred lower limit is 800, and the further preferred upper limit is 3600.
[0053] In addition, by setting the average degree of polymerization to 2000 or less, residual stress can be reduced by adjusting the content of the plasticizer, etc. The upper limit of the average degree of polymerization is more preferably 1800, further preferably 1500, and particularly preferably 900.
[0054] When the polyvinyl alcohol is acetalized with an aldehyde in the presence of a catalyst, a solution containing the polyvinyl alcohol may be used. Examples of the solvent used in the solution containing the polyvinyl alcohol include water.
[0055] The aldehyde is not particularly limited, but generally, aldehydes having 1 to 10 carbon atoms are preferably used.
[0056] The aldehyde having a carbon number of 1 to 10 is not particularly limited and may be a straight-chain aldehyde or a branched aldehyde. Examples of the aldehyde having a carbon number of 1 to 10 include n-butyraldehyde, isobutyraldehyde, n-valeraldehyde, 2-ethylbutyraldehyde, n-hexanal, n-octanal, n-nonanal, n-decanal, formaldehyde, acetaldehyde, benzaldehyde, and the like. Among them, n-butyraldehyde, n-hexanal, and n-valeraldehyde are preferred, and n-butyraldehyde is more preferred. These aldehydes may be used alone or in combination of two or more.
[0057] That is, the polyvinyl acetal preferably contains polyvinyl butyral (when the aldehyde is n-butyraldehyde, the polyvinyl acetal is referred to as polyvinyl butyral). By using the polyvinyl butyral, the adhesion of the filling bonding material to the glass can be properly exhibited, and the light resistance, weather resistance, etc. can be improved. In addition, two or more polyvinyl acetals can be used in combination as needed.
[0058] From the perspective of excellent height difference tracking and anti-foaming properties, the polyvinyl acetal preferably has less intermolecular crosslinking. If the polyvinyl acetal has less intermolecular crosslinking, even if the molecular weight, acetyl group content, acetalization degree, etc. of the polyvinyl acetal are the same, a filling and bonding material with better height difference tracking and anti-foaming properties can be obtained. In addition, if the molecular weight of the polyvinyl acetal is large, better anti-scattering properties and reprocessing properties can be obtained.
[0059] As a method for obtaining such a polyvinyl alcohol acetal with less intermolecular crosslinking, for example, the following method is preferred: in order to prevent the main chains of adjacent polyvinyl alcohols from being crosslinked, the above-mentioned aldehyde is not added in excess before or during the acetalization reaction using the above-mentioned aldehyde. If the above-mentioned aldehyde is added in an amount exceeding the amount required for acetalization, the degree of crosslinking increases.
[0060] The preferred lower limit of the content rate (hydroxyl amount) of the hydroxyl group of the above-mentioned polyvinyl acetal is 16 mol%, and the preferred upper limit is 45 mol%. If the above-mentioned hydroxyl amount is more than 16 mol%, the bonding strength between the filling bonding material and the glass is improved. If the above-mentioned hydroxyl amount is less than 45 mol%, the flexibility of the above-mentioned polyvinyl acetal increases, and the operability is improved. In addition, the compatibility of the above-mentioned polyvinyl acetal and the above-mentioned plasticizer is improved, and the height difference followability of the filling bonding material is improved. The more preferred lower limit of the above-mentioned hydroxyl amount is 18 mol%, the further preferred lower limit is 20 mol%, the particularly preferred lower limit is 22 mol%, the more preferred upper limit is 40 mol%, the further preferred upper limit is 38 mol%, the further preferred upper limit is 36 mol%, and the particularly preferred upper limit is 35 mol%.
[0061] It should be noted that the hydroxyl amount of polyvinyl acetal is a value obtained by dividing the amount of ethylene groups bonded to the hydroxyl groups by the total amount of ethylene groups in the main chain and expressing the molar ratio as a percentage (mol %). The amount of ethylene groups bonded to the hydroxyl groups can be obtained, for example, by a method according to JIS K6728 "Testing methods for polyvinyl butyral".
[0062] The preferred lower limit of the acetylation degree (acetyl amount) of the above-mentioned polyvinyl acetal is 0.1 mol%, and the preferred upper limit is 30 mol%. If the above-mentioned acetyl amount is 0.1 mol% or more, the compatibility of the above-mentioned polyvinyl acetal with the above-mentioned plasticizer is improved, and the height difference followability of the filling bonding material is improved. If the above-mentioned acetyl amount is 30 mol% or less, the moisture resistance of the above-mentioned polyvinyl acetal is improved. In addition, if the above-mentioned acetyl amount is 30 mol% or less, the reduction of the reaction efficiency when manufacturing the above-mentioned polyvinyl acetal can be suppressed. The more preferred lower limit of the above-mentioned acetyl amount is 0.2 mol%, the further preferred lower limit is 0.3 mol%, the more preferred upper limit is 24 mol%, the further preferred upper limit is 20 mol%, the further preferred upper limit is 19.5 mol%, and the particularly preferred upper limit is 15 mol%.
[0063] It should be noted that the amount of acetyl groups in polyvinyl acetal is a value expressed as a percentage (mol %) of the molar ratio obtained by subtracting the amount of ethylene groups bonded to the acetal group and the amount of ethylene groups bonded to the hydroxyl group from the total amount of ethylene groups in the main chain. The amount of ethylene groups bonded to the acetal group can be measured, for example, according to JIS K6728 "Testing methods for polyvinyl butyral".
[0064] As a method for adjusting the acetyl group content of the polyvinyl acetal to the above range, for example, a method of adjusting the saponification degree of the polyvinyl alcohol can be cited. That is, the acetyl group content of the polyvinyl acetal depends on the saponification degree of the polyvinyl alcohol. If a polyvinyl alcohol with a low saponification degree is used, the acetyl group content of the polyvinyl acetal increases, and if a polyvinyl alcohol with a high saponification degree is used, the acetyl group content of the polyvinyl acetal decreases.
[0065] The preferred lower limit of the acetalization degree of the above-mentioned polyvinyl acetal is 50 mol%, and the preferred upper limit is 85 mol%. If the above-mentioned acetalization degree is more than 50 mol%, the compatibility of the above-mentioned polyvinyl acetal and the above-mentioned plasticizer is improved. If the above-mentioned acetalization degree is below 85 mol%, the reaction time required for the manufacture of the above-mentioned polyvinyl acetal can be shortened. The more preferred lower limit of the above-mentioned acetalization degree is 54 mol%, the further preferred lower limit is 58 mol%, and the particularly preferred lower limit is 60 mol%. The more preferred upper limit of the above-mentioned acetalization degree is 82 mol%, the further preferred upper limit is 79 mol%, and the particularly preferred upper limit is 77 mol%.
[0066] It should be noted that the degree of acetalization of polyvinyl acetal is a value expressed as a percentage (mol %) of the molar ratio obtained by dividing the amount of ethylene groups to which the acetal group is bonded by the total amount of ethylene groups in the main chain. The degree of acetalization can be calculated by measuring the amount of acetyl groups and the amount of vinyl alcohol (the content of hydroxyl groups) according to JIS K6728 "Testing methods for polyvinyl butyral", calculating the molar ratio from the obtained measurement results, and then subtracting the amount of acetyl groups and the amount of vinyl alcohol from 100 mol %.
[0067] As a method for adjusting the acetalization degree of the polyvinyl acetal, for example, there can be mentioned a method of adjusting the amount of the aldehyde added. If the amount of the aldehyde added is reduced, the acetalization degree of the polyvinyl acetal decreases, and if the amount of the aldehyde added is increased, the acetalization degree of the polyvinyl acetal increases.
[0068] The glass transition temperature (Tg) of the polyvinyl acetal is not particularly limited, but is preferably 10° C. or higher from the viewpoint of obtaining more excellent anti-scattering property and reprocessability.
[0069] The above-mentioned plasticizer is not particularly limited, and conventionally known plasticizers can be used, and can be used alone or in combination of two or more. As the above-mentioned plasticizer, for example, organic acid ester plasticizers such as monobasic organic acid esters and polybasic organic acid esters, organic phosphoric acid plasticizers, organic phosphorous acid plasticizers, etc. can be cited. Among them, organic acid ester plasticizers are preferred. The above-mentioned plasticizer is preferably a liquid plasticizer.
[0070] The monobasic organic acid ester is not particularly limited, and examples thereof include glycol esters obtained by reacting a monobasic organic acid with a glycol. Examples of the monobasic organic acid include butyric acid, isobutyric acid, hexanoic acid, 2-ethylbutyric acid, heptanoic acid, n-octanoic acid, 2-ethylhexanoic acid, nonanoic acid (n-nonanoic acid), and capric acid. Examples of the glycol include triethylene glycol, tetraethylene glycol, and tripropylene glycol. The polybasic organic acid ester is not particularly limited, and examples thereof include ester compounds obtained by reacting a polybasic organic acid such as adipic acid, sebacic acid, and azelaic acid with an alcohol having a linear or branched structure and having 4 to 8 carbon atoms.
[0071] The organic acid ester plasticizer is preferably a diester plasticizer represented by the following formula (1). By using the diester plasticizer, the moldability of the filling and bonding material is improved.
[0072] R 1 -CO-(-R 3 -O-)p-CO-R 2 (1)
[0073] In formula (1), R 1 and R 2Each represents an organic group having 5 to 10 carbon atoms (preferably 6 to 10 carbon atoms), R 3 represents an ethylene group, an isopropylene group or an n-propylene group, and p represents an integer of 3 to 10.
[0074] Specific examples of the organic acid ester plasticizer include triethylene glycol-di-2-ethylbutyrate, triethylene glycol-di-2-ethylhexanoate, triethylene glycol dioctanoate, triethylene glycol di-n-octanoate, triethylene glycol-di-n-heptanoate, tetraethylene glycol-di-n-heptanoate, tetraethylene glycol-di-2-ethylhexanoate, dibutyl sebacate, dioctyl azelate, dibutyl carbitol adipate, ethylene glycol di-2-ethylbutyrate, 1,3-propylene glycol dioctanoate ... Diol di-2-ethylbutyrate, 1,4-butanediol di-2-ethylbutyrate, diethylene glycol di-2-ethylbutyrate, diethylene glycol di-2-ethylhexanoate, dipropylene glycol di-2-ethylbutyrate, triethylene glycol di-2-ethylvalerate, tetraethylene glycol di-2-ethylbutyrate, diethylene glycol dioctanoate, dihexyl adipate, dioctyl adipate, hexylcyclohexyl adipate, diisononyl adipate, heptylnonyl adipate, etc. In addition, oil-modified sebacic acid (Japanese: oil-modified sebacic acid alkyd), a mixture of a phosphate and an adipate, a mixed type adipate made from an alkyl alcohol having 4 to 9 carbon atoms and a cyclic alcohol having 4 to 9 carbon atoms, etc. can be mentioned.
[0075] The organic phosphoric acid plasticizer is not particularly limited, and examples thereof include tributoxyethyl phosphate, isodecylphenyl phosphate, and triisopropyl phosphate.
[0076] Among the above plasticizers, at least one selected from dihexyl adipate (DHA), triethylene glycol-di-2-ethylhexanoate (3GO), tetraethylene glycol-di-2-ethylhexanoate (4GO), triethylene glycol-di-2-ethylbutyrate (3GH), tetraethylene glycol-di-2-ethylbutyrate (4GH), tetraethylene glycol-di-n-heptanoate (4G7) and triethylene glycol-di-n-heptanoate (3G7) is preferred. In addition, triethylene glycol-di-2-ethylbutyrate (3GH), triethylene glycol-di-n-heptanoate (3G7) and triethylene glycol-di-2-ethylhexanoate (3GO) are more preferred, and triethylene glycol-di-2-ethylhexanoate is further preferred.
[0077] The content of the plasticizer relative to the polyvinyl acetal is not particularly limited, but the preferred lower limit is 5 parts by weight and the preferred upper limit is 75 parts by weight relative to 100 parts by weight of the polyvinyl acetal. If the content is within the above range, it is easy to achieve both anti-scattering properties and height difference followability of the filling and bonding material.
[0078] If the above content is less than 5 parts by weight, the formability of the filling bonding material is sometimes reduced. If the above content exceeds 75 parts by weight, the transparency of the filling bonding material is sometimes reduced, or the above plasticizer oozes out. The more preferred lower limit of the above plasticizer is 10 parts by weight, the further preferred lower limit is 15 parts by weight, and the particularly preferred lower limit is 20 parts by weight. The more preferred upper limit of the above plasticizer is 65 parts by weight, and the further preferred upper limit is 55 parts by weight. In addition, when the content of the above plasticizer relative to the above polyvinyl acetal increases, bubbles sometimes occur in a high temperature and high humidity environment, and the optical quality deteriorates. In order to suppress the degradation of optical quality under a high temperature and high humidity environment, the content of the above plasticizer relative to 100 parts by weight of the above polyvinyl acetal is preferably less than 50 parts by weight. The more preferred upper limit of the above plasticizer from this viewpoint is 40 parts by weight, and the particularly preferred upper limit is 30 parts by weight.
[0079] It should be noted that since the polyvinyl acetal generates cohesive force, the content of the plasticizer is preferably small. That is, it is preferred to improve the compatibility of the polyvinyl acetal and the plasticizer and reduce the content of the plasticizer. Thus, the anti-scattering property can be improved.
[0080] As a method for improving the compatibility of the polyvinyl acetal and the plasticizer, for example, a method of increasing the acetalization degree of the polyvinyl acetal and a method of increasing the amount of acetyl groups are preferred. In addition, a method of reducing the blockiness of the hydroxyl group of the polyvinyl acetal is also preferred. As a method for suppressing the blockiness of the hydroxyl group, a method of reducing the aging temperature is preferred.
[0081] In the filling bonding material of the present invention, the content of the polyvinyl acetal is preferably 50% by weight or more. If the content is 50% by weight or more, it is easy to take into account both the anti-scattering property and the height difference followability of the filling bonding material. The more preferred lower limit of the content is 60% by weight, the further preferred lower limit is 70% by weight, the particularly preferred lower limit is 80% by weight, and the most preferred lower limit is 90% by weight.
[0082] The upper limit of the content of the polyvinyl acetal is not particularly limited, and may be 100% by weight.
[0083] The ethylene-vinyl acetate copolymer is not particularly limited, but preferably has a vinyl acetate content of 5 to 50% by weight.
[0084] The acid-modified olefin is not particularly limited, and examples thereof include acid-modified polypropylenes such as maleic anhydride-modified polypropylene, maleic acid-modified polypropylene, and acrylic acid-modified polypropylene.
[0085] The glass transition temperature (Tg) of the above-mentioned (meth) acrylic copolymer is preferably higher than room temperature of about 23°C. If the above-mentioned glass transition temperature (Tg) is lower than room temperature of about 23°C, it is sometimes difficult to form thick films and shapes of unequal thickness. It should be noted that, in this specification, the glass transition temperature refers to: the temperature at which the loss tangent tanδ measured by dynamic viscoelasticity measurement shows a maximum value. In addition, tanδ can be calculated as a value obtained by dividing the loss modulus (G") measured by the viscoelasticity measuring device described later by the storage modulus (G') (tanδ = G' / G").
[0086] The (meth)acrylic copolymer preferably has a storage modulus of 1.0×10 4 Pa or more. If the above storage modulus is 1.0×10 4 Pa or more, the filling and bonding material has excellent cohesive force, and the processability, handling properties, shape retention, etc. become good. A more preferred lower limit of the storage modulus at 20°C is 5.0×10 4 Pa.
[0087] The (meth)acrylic copolymer preferably has a storage modulus of 1.0×10 6 Pa or less. If the above storage modulus is 1.0×10 6 Pa or less, the initial adhesion (tackiness) of the filling and bonding material required for bonding becomes good. The more preferred upper limit of the storage elastic modulus at 20°C is 5.0×10 5 Pa.
[0088] The (meth)acrylic copolymer preferably has a storage modulus of 5.0×10 4 Pa or less. If the storage modulus is 5.0×10 4 Pa or less, the filling bonding material heated during bonding can flow within a predetermined time (for example, from several seconds to several minutes) to follow the height difference of the adherend without forming voids.
[0089] The storage modulus of the (meth)acrylic copolymer can be adjusted by appropriately changing the type, molecular weight and blending ratio of the monomers constituting the (meth)acrylic copolymer, the degree of polymerization of the (meth)acrylic copolymer, the type and blending ratio of the plasticizer, and the like.
[0090] For example, if an ethylenically unsaturated monomer having an acidic group is used, the storage modulus tends to be higher. In addition, for example, if the amount of (meth)acrylic acid alkyl esters having an alkyl carbon number of 2 to 26 or the amount of (meth)acrylic acid hydroxyalkyl esters having an alkyl carbon number of 4 or less is increased, the storage modulus tends to decrease. In addition, if the amount of (meth)acrylic acid esters containing groups formed by combining ethylene oxide, propylene oxide, butylene oxide, and a plurality of them is increased, or the amount of (meth)acrylic acid esters having a carbonyl group in an alcohol residue is increased, the storage modulus tends to decrease. In addition, if the degree of polymerization of the above-mentioned (meth)acrylic copolymer is increased, the storage modulus tends to increase.
[0091] It should be noted that the storage modulus of the (meth)acrylic copolymer can be measured using a dynamic viscoelasticity measuring apparatus such as ARES-G2 (manufactured by TAINSTRUMENTS) or DVA-200 (manufactured by IT Measurement & Control Co., Ltd.) under the conditions of raising the temperature from -50°C to 100°C at a heating rate of 3°C / min, a frequency of 1 Hz, and a shear strain of 1%.
[0092] Examples of the silicone resin include polymers having a main chain including a siloxane bond. To obtain such a polymer, for example, a curable, non-curable, or semi-cured B-stage polyorganosiloxane composition may be used.
[0093] Examples of the curable polyorganosiloxane composition include compositions containing alkenyl-containing polyorganosiloxane, polyorganohydrogensiloxane, and platinum-based catalysts (compounds of platinum group elements such as platinum, rhodium, and palladium). The curable polyorganosiloxane composition may further contain a stabilizer, a diluent, a tackifier, an inorganic filler, and the like.
[0094] It should be noted that the alkenyl-containing polyorganosiloxane is the base polymer in the curable polyorganosiloxane composition, and in the presence of a platinum catalyst, an addition reaction occurs with the hydrosilyl group in the polyorganohydrogensiloxane to form a crosslink. By including the above-mentioned components, a stable three-dimensional structure brought about by crosslinking during curing can be ensured, curing shrinkage can be controlled, and good optical properties can be ensured.
[0095] In addition, as the curing mechanism of the above-mentioned silicone resin, for example, the dehydration condensation reaction of silanol groups, the dehydrogenation condensation reaction of silanol groups and hydrogen atoms bonded to silicon atoms, the dealcoholization condensation reaction based on alkoxy groups bonded to silicon atoms and silanol groups, the deacetyl condensation reaction based on acetoxy groups bonded to silicon atoms and silanol groups, and the like. In addition, the hydrosilylation reaction of alkenyl groups bonded to silicon atoms and hydrogen atoms bonded to silicon atoms can also be cited. In addition, the free radical reaction based on acryloyl or methacryloyl groups, the free radical reaction based on organic peroxides, and the like can also be cited. The silicone resin can be obtained by these reactions. For example, a thermosetting silicone resin can be used.
[0096] The urethane resin is generally a reaction product of a polyol component and a polyisocyanate component.
[0097] The above-mentioned polyol component is not particularly limited, but preferably has an olefin skeleton. As the above-mentioned polyol component having an olefin skeleton, for example, polybutadiene polyols such as 1,2-polybutadiene polyol, polyisoprene polyol, and polyol components after saturating their double bonds with hydrogen or halogen. In addition, the above-mentioned polyol component can be: a polyol obtained by copolymerizing the above-mentioned polybutadiene polyol with an olefin compound such as styrene, ethylene, vinyl acetate, acrylate, or a hydride thereof. The above-mentioned polyol component can be a polyol component having a linear structure or a polyol component having a branched structure. These polyol components can be used alone or in combination of two or more.
[0098] The number average molecular weight of the polyol component is not particularly limited, but is preferably 300 or more and 5000 or less. If the number average molecular weight is less than 300, the reaction between the polyol component and the polyisocyanate component is too fast, and sometimes the forming of the filling bonding material becomes difficult, or the flexibility is reduced and becomes brittle. If the number average molecular weight exceeds 5000, the viscosity of the polyol component becomes too high, and sometimes the forming of the filling bonding material becomes difficult, or the filling bonding material crystallizes and becomes turbid. The number average molecular weight is more preferably 500 or more and 3000 or less.
[0099] The polyisocyanate component is not particularly limited, but is preferably a modified polyisocyanate obtained by reacting an aliphatic and / or alicyclic polyisocyanate having an isocyanate group with an ether compound having an ethylene oxide unit.
[0100] By using the above-mentioned aliphatic and / or alicyclic polyisocyanates, a filling and bonding material with less coloration and high transparency can be obtained. In addition, by setting it as a modified body obtained by allowing the above-mentioned ether compound having ethylene oxide units to participate in the reaction, the polyisocyanate component can suppress whitening through the action of the hydrophilic part (ethylene oxide unit) and can exert compatibility with low-polarity plasticizers and the like through the action of the hydrophobic part (other units).
[0101] Specific examples of the aliphatic and / or alicyclic polyisocyanates include hexamethylene diisocyanate, isophorone diisocyanate, and modified forms thereof. Examples of the ether compound having an oxyethylene unit include oxyethylene adducts of alcohols, phenols, and / or amines. Among them, it is preferred that the ether compound has 6 or more oxyethylene units per molecule from the viewpoint of improving hydrophilicity. The content of the oxyethylene unit is preferably 1% by weight or more and 20% by weight or less relative to the total amount of the urethane resin.
[0102] The number of isocyanate groups per molecule of the modified polyisocyanate is preferably 2.0 or more on average. If the number of isocyanate groups is less than 2.0 on average, the reaction between the polyol component and the polyisocyanate component may become insufficient due to a decrease in crosslinking density.
[0103] The α ratio (the number of moles of OH groups from the polyol component / the number of moles of NCO groups from the polyisocyanate component) of the urethane resin is preferably greater than 1. If the α ratio is less than 1, the polyisocyanate component is excessive relative to the polyol component, so the urethane resin sometimes becomes hard, and the height difference followability and adhesion of the filling bonding material are reduced. The α ratio more preferably satisfies 1<α<2.0. If the α ratio is greater than 2.0, the reaction of the polyol component and the polyisocyanate component sometimes becomes insufficient.
[0104] The filling and bonding material of the present invention may further contain a reactive diluent and a photopolymerization initiator.
[0105] By using the above-mentioned reactive diluent and the above-mentioned photopolymerization initiator, it is possible to exhibit high height difference tracking performance (anti-foaming performance) when the filling bonding material is attached, and at the same time, it is cross-linked by photopolymerization reaction, thereby improving the anti-scattering performance. If the above-mentioned reactive diluent is reacted by irradiating light after attaching the adherend, the above-mentioned reactive diluent will not remain or ooze out.
[0106] In this specification, the reactive diluent refers to a reagent that is compatible with the material of the filling and bonding material of the present invention and that reacts with the reactive diluent to crosslink and cure by irradiation with light. In this specification, the reactive diluent is not included in the above-mentioned plasticizer.
[0107] Examples of the reactive diluent include reactive diluents having reactive double bonds such as monofunctional, difunctional, or trifunctional or higher (meth) acrylic monomers and their oligomers, and epoxy reactive diluents such as glycidyl ethers. Among them, reactive diluents having reactive double bonds are preferred because they are highly compatible with the material of the filling and bonding material of the present invention and can be easily crosslinked and cured by combining with a photopolymerization initiator.
[0108] The content of the above-mentioned reactive diluent is not particularly limited, but the preferred lower limit is 0.5 weight %, and the preferred upper limit is 50 weight %. If the above-mentioned content is less than 0.5 weight %, the filling and bonding material sometimes cannot exert high height difference following property (anti-foaming property). If the above-mentioned content exceeds 50 weight %, the toughness, bending rigidity and adhesion to glass etc. of the filling and bonding material sometimes decrease, and the anti-scattering property decreases. The more preferred lower limit of the content of the above-mentioned reactive diluent is 1 weight %, the more preferred upper limit is 30 weight %, the further preferred lower limit is 2 weight %, the further preferred upper limit is 20 weight %, the particularly preferred lower limit is 4 weight %, and the particularly preferred upper limit is 10 weight %.
[0109] As the (meth)acrylic monomer as the reactive diluent having a reactive double bond, a monofunctional, bifunctional, or trifunctional or higher-functional (meth)acrylic monomer can be used.
[0110] Examples of the monofunctional (meth)acrylic monomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, diethylene glycol monoethyl ether (meth)acrylate, isobornyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, 2-acryloyloxyethyl-2-hydroxypropyl phthalate, and 2-methacryloyloxyethyl-2-hydroxypropyl phthalate.
[0111] Examples of the bifunctional (meth)acrylic monomer include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol dimethacrylate, 1,9-nonanediol diacrylate, polytetramethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, and 2,2-bis[4-(methacryloyloxyethoxy)phenyl]propane di(meth)acrylate.
[0112] Examples of the trifunctional or higher-functional (meth)acrylic monomer include trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol trimethacrylate, pentaerythritol tetramethacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, tris(2-acryloyloxyethyl)phosphate, tetramethylolmethane tri(meth)acrylate, tetramethylolpropane tetra(meth)acrylate, triallyl isocyanurate and derivatives thereof.
[0113] The (meth) acrylic monomer as the reactive diluent having a reactive double bond may be used alone or in combination of two or more. Among them, monofunctional (meth) acrylic monomers are preferred from the viewpoint of excellent compatibility with the material (especially polyvinyl acetal) of the filling bonding material of the present invention. More specifically, methyl (meth) acrylate, ethyl (meth) acrylate, propyl (meth) acrylate, butyl (meth) acrylate, 2-hydroxyethyl (meth) acrylate, etc. are preferred.
[0114] The (meth)acrylic oligomer as the reactive diluent having a reactive double bond may be an oligomer formed by bonding a plurality of the above-mentioned (meth)acrylic monomers. Among them, the (meth)acrylic oligomer formed by the above-mentioned acrylic monomers is suitable from the viewpoint of excellent compatibility with the material (especially polyvinyl acetal) of the filling bonding material of the present invention.
[0115] Furthermore, it is preferred that the (meth)acrylic monomer also contains a (meth)acrylate having a diol skeleton.
[0116] By using the above-mentioned (meth)acrylate having a diol skeleton, a filling bonding material having a low initial haze value and a low haze value after a high temperature and high humidity test and high transparency can be obtained. In addition, the above-mentioned (meth)acrylate having a diol skeleton has excellent compatibility with the material of the filling bonding material of the present invention and excellent photoreactivity. In addition, by using the above-mentioned (meth)acrylate having a diol skeleton, the amount of double bonds in the filling bonding material can be reduced, and the curing shrinkage rate during curing can also be reduced.
[0117] Examples of the (meth)acrylate having a diol skeleton include monofunctional (meth)acrylates, bifunctional (meth)acrylates, and trifunctional or higher (meth)acrylates. Specific examples of the monofunctional (meth)acrylate include methoxypolyethylene glycol (meth)acrylate having 2 to 23 ethylene groups, phenoxydiethylene glycol (meth)acrylate, and phenoxyhexaethylene glycol (meth)acrylate. Examples of the (meth)acrylate include phenoxypolyethylene glycol (meth)acrylate having 2 to 14 ethylene groups, and methoxypolypropylene glycol (meth)acrylate having 2 to 14 propylene groups. Examples of the bifunctional (meth)acrylate include polypropylene glycol diacrylate, diethylene glycol di(meth)acrylate having 2 to 23 ethylene groups, ethoxylated bisphenol A diacrylate having 2 to 14 ethylene groups, and polypropylene glycol diacrylate having 2 to 14 propylene groups. Examples of the above-mentioned trifunctional or higher (meth)acrylates include: EO-modified trimethylolpropane tri(meth)acrylate, PO-modified trimethylolpropane tri(meth)acrylate, EO, PO-modified trimethylolpropane tri(meth)acrylate, etc. In addition, examples include: dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, pentaerythritol tetra(meth)acrylate, etc. Here, "EO" represents ethylene oxide, and the EO-modified compound represents a compound having a block structure of ethylene oxide groups. In addition, "PO" represents propylene oxide, and the PO-modified compound represents a compound having a block structure of propylene oxide groups. These (meth)acrylates having a diol skeleton can be used alone or in combination of two or more.
[0118] Examples of commercially available products of the (meth)acrylate having a diol skeleton include the following commercial products manufactured by Shin-Nakamura Chemical Industry Co., Ltd. That is, NK ester AM-90G, AM-130G, M-90G, A-200, A-600, APG-400, APG-700, A-GLY-9E, A-TMPT-3EO, A-TMPT-9EO, A-TMPT-3PO, A-TMPT-6PO, ATM-35E, and the like.
[0119] In addition, it is preferred that the (meth)acrylic monomer also contains a phosphate-based (meth)acrylate.
[0120] By using the above-mentioned phosphate-based (meth)acrylate, the tanδ value can be increased while the storage modulus of the filling bonding material is maintained at a high level, and a filling bonding material with particularly excellent impact resistance can be obtained. In addition, a filling bonding material with less coloring and high transparency can be obtained. It is believed that the reason is that among the above-mentioned (meth)acrylic monomers, the phosphate-based (meth)acrylate has excellent compatibility with the materials of the filling bonding material of the present invention (especially polyvinyl acetal). It should be noted that since the above-mentioned phosphate-based (meth)acrylate has excellent compatibility with the materials of the filling bonding material of the present invention, it is also possible to obtain an effect of suppressing the viscosity of the filling bonding material and excellent photoreactivity.
[0121] The phosphate (meth)acrylate is not particularly limited, but a phosphate (meth)acrylate represented by the following general formula (2) is suitable. These phosphate (meth)acrylates may be used alone or in combination of two or more.
[0122]
Chemistry 1
[0123]
[0124] In the general formula (2), Z 1 Indicates A 2 -O-X 2 -, a substituent or hydrogen atom without a polymerizable double bond, Z 2 Indicates A 3 -O-X 3 - A substituent or hydrogen atom that does not have a polymerizable double bond. 1 , A 2 and A 3 represents acryloyl or methacryloyl, X 1 , X 2 and X 3 It represents an alkylene group, an alkyleneoxy group, an alkyleneoxycarbonyl group, an alkylenecarbonyloxy group, or a combination thereof.
[0125] Examples of commercially available products of the phosphate-based (meth)acrylates include 2-(methacryloyloxy)ethyl phosphate (SR9050 manufactured by Sartomer), tris[2-(methacryloyloxy)ethyl]phosphate (SR9051 manufactured by Sartomer), and tris[2-(acryloyloxy)ethyl]phosphate (SR9053 manufactured by Sartomer). In addition, examples include KAYAMER series manufactured by Nippon Kayaku Co., Ltd. and Phosmer series manufactured by Unichemika Co., Ltd.
[0126] When the filling and bonding material of the present invention contains the (meth)acrylate having a diol skeleton or the phosphate-based (meth)acrylate, a reactive diluent having a reactive double bond other than these may be used in combination.
[0127] As the above-mentioned photopolymerization initiator, it is sufficient to appropriately select according to the type of the above-mentioned reactive diluent. For example, when using monofunctional, difunctional or trifunctional or higher (meth) acrylic monomers and their oligomers as the above-mentioned reactive diluent, benzoin-based compounds, alkyl phenone (Japanese: アルキルフェノン)-based compounds, thioxanthone-based compounds, acetophenone-based compounds, acyl sulfinyl (Japanese: アシルスルフィン)-based compounds, persulfates, organic peroxides, azo compounds, etc. can be used. These photopolymerization initiators can be used alone or in combination of two or more.
[0128] The amount of the photopolymerization initiator is not particularly limited, but the preferred lower limit relative to 100 parts by weight of the reactive diluent is 0.01 parts by weight, and the preferred upper limit is 5 parts by weight. If the amount of the photopolymerization initiator is less than 0.01 parts by weight, the reactive diluent may not be reacted sufficiently, or the reaction may take a long time. Even if the amount of the photopolymerization initiator exceeds 5 parts by weight, the reactivity may not be particularly improved, and problems such as the oozing of the photopolymerization initiator may occur. The more preferred lower limit of the content of the photopolymerization initiator is 0.1 parts by weight, and the more preferred upper limit is 2 parts by weight.
[0129] In the filling and bonding material of the present invention, the amount of double bonds in all compounds except the above-mentioned photopolymerization initiator is preferably less than 2.9 mmol / g. Thus, the curing shrinkage during curing can be reduced, and the occurrence of uneven thickness and uneven color caused by curing shrinkage can be reduced. It should be noted that the occurrence of such uneven thickness and uneven color (especially uneven color on the side in contact with the display device) can lead to a reduction in the display performance of the display device. The more preferred upper limit of the above-mentioned double bond amount is 2.4 mmol / g, and the further preferred upper limit is 2.2 mmol / g.
[0130] The lower limit of the double bond amount is not particularly limited, but is preferably 1.5 mmol / g or more. This can improve the height difference followability and anti-scattering properties of the filling bonding material. A more preferred lower limit of the double bond amount is 1.7 mmol / g, and a further preferred lower limit is 2.0 mmol / g.
[0131] It should be noted that in this specification, for all compounds contained in the filling and bonding material of the present invention except the above-mentioned photopolymerization initiator, the above-mentioned double bond amount can be calculated based on the addition amount and molecular weight of each compound having double bonds. In addition, the above-mentioned double bond amount can also be calculated by the following method: by determining the iodine value according to the method of JIS K 0070, and calculating the double bond amount from the value. In addition, it can also be measured by the following method: using a gas chromatograph-mass spectrometer (GC-MS) to analyze the composition of the filling and bonding material, and calculating the addition amount and molecular weight of the above-mentioned compound having double bonds.
[0132] The curing shrinkage of the filling bonding material of the present invention during curing (when the reactive diluent is reacted by irradiation with light) is not particularly limited, but is preferably 2% or less. If the curing shrinkage is 2% or less, the occurrence of uneven thickness and uneven color (especially uneven color on the side in contact with the display device) caused by such curing shrinkage, which is related to the reduction of the display performance of the display device, can be reduced. The curing shrinkage is more preferably 1% or less.
[0133] It should be noted that in this specification, the above-mentioned curing shrinkage can be calculated using the density (dl) of the filling bonding material before light irradiation and the density (df) after light irradiation. The density of the filling bonding material before and after light irradiation can be measured according to JIS K 7112, and a high-precision electronic densitometer (made by Alfa Mirage, SD-200L) or a high-precision dry automatic densitometer (made by Micromeritics, ACCUPYC II 1340-1CC) can be used. The curing shrinkage is calculated by the following calculation formula.
[0134] Curing shrinkage (%) = (df-dl) / df×100
[0135] The filling and bonding material of the present invention may further contain an ultraviolet absorber.
[0136] By using the above-mentioned ultraviolet absorber, the light resistance of the filling and bonding material can be improved. In particular, if an ultraviolet absorber is used that does not absorb light (ultraviolet) of a wavelength at which the above-mentioned reactive diluent reacts, but absorbs light (ultraviolet) of a wavelength different from the wavelength at which the above-mentioned reactive diluent reacts, the reaction of the above-mentioned reactive diluent will not be hindered. Examples of such ultraviolet absorbers include malonate-based ultraviolet absorbers and oxalylanilide-based ultraviolet absorbers.
[0137] The filling bonding material of the present invention may contain known additives such as an adhesion regulator, a tackifier resin, a plasticizer, an emulsifier, a softener, fine particles, a filler, a pigment, a dye, a silane coupling agent, an antioxidant, a surfactant, and a wax as required.
[0138] The glass transition temperature (Tg) of the filling bonding material of the present invention is preferably above 10°C. By setting the glass transition temperature (Tg) to above 10°C, unnecessary adhesion will not be exhibited during transportation and use, and the handling is excellent. The preferred lower limit of the glass transition temperature (Tg) is 15°C, and the more preferred lower limit is 20°C. In addition, the glass transition temperature (Tg) of the filling bonding material of the present invention is preferably below 60°C. By setting the glass transition temperature (Tg) to below 60°C, high temperature is not required, bonding can be performed even at relatively low temperatures, and thermal damage to the bonded components (adherends) can be suppressed. The preferred upper limit of the glass transition temperature (Tg) is 50°C, and the more preferred upper limit is 40°C.
[0139] It should be noted that the glass transition temperature referred to herein refers to the temperature at which the loss tangent tanδ measured by dynamic viscoelasticity measurement shows a maximum value. In addition, tanδ can be calculated from the storage modulus (G') and loss modulus (G") measured by a dynamic viscoelasticity measuring device under the conditions of heating the temperature from -50°C to 100°C at a heating rate of 3°C / min, a frequency of 1 Hz, and a shear strain of 1% (tanδ = G' / G").
[0140] The storage modulus of the filling bonding material of the present invention at 20°C is preferably 1×10 4 Pa or above.
[0141] By making the storage modulus at 20°C within the above range, the forming or processing of the filling bonding material at room temperature becomes easy, and the unequal thickness shape can be maintained at room temperature. On the other hand, by performing crimping while heating, it is also possible to fully follow the height difference of the decorative printing part (the height difference of the printing part on the back side of the surface protection panel) and the wiring height difference (the height difference of the wiring formed on the touch panel). In addition, in the case where optical devices are damaged due to impact such as accidental dropping, the effect of suppressing the scattering of glass fragments can also be expected. The storage modulus at 20°C is more preferably 2×10 5 Pa or more, more preferably 1×10 6 Pa or more, more preferably 1×10 7 Pa or more, particularly preferably 3×10 7 Pa or above.
[0142] The upper limit of the storage modulus at 20°C is not particularly limited, but a preferred upper limit is 1×10 10 Pa. If the storage modulus at 20°C exceeds 1×10 10 Pa, the filling and bonding material may become too hard, and the adhesion and workability may be reduced. The more preferred upper limit of the storage elastic modulus at 20°C is 1×109 Pa.
[0143] In addition, the storage modulus of the filling bonding material of the present invention at 80°C is preferably 1×10 6 Pa or less. If the storage modulus at 80°C exceeds 1×10 6 Pa, even if heated during bonding, the filling bonding material may not be able to follow the deformation stress, and bubbles are likely to remain in the height difference. The more preferred upper limit of the storage modulus at 80°C is 9×10 5 Pa, and a further preferred upper limit is 7×10 5 Pa, and the upper limit is particularly preferably 5×10 5 Pa.
[0144] The lower limit of the storage modulus at 80°C is not particularly limited, but a preferred lower limit is 1×10 3 Pa. If the storage modulus at 80°C is less than 1×10 3 Pa, the heat-resistant mechanical strength as a filling bonding material may not be maintained. A more preferred lower limit of the storage elastic modulus at 80°C is 1×10 4 Pa, and a further preferred lower limit is 5×10 4 Pa, the lower limit of which is particularly preferred is 1×10 5 Pa.
[0145] Furthermore, since the filling and bonding material of the present invention has such elastic modulus characteristics, it can easily fill the gaps between layers when heated to about 80° C. during lamination, and has excellent workability. It can also more easily fill the gaps between layers when pressurized during heating.
[0146] It should be noted that the storage modulus of the filling bonding material can be measured using a dynamic viscoelasticity measuring device such as ARES-G2 (manufactured by TA INSTRUMENTS) or DVA-200 (manufactured by IT Measurement and Control Co., Ltd.) under the conditions of raising the temperature from -50°C to 100°C at a heating rate of 3°C / min, a frequency of 1 Hz, and a shear strain of 1%.
[0147] As a method for adjusting the storage modulus of the filling bonding material of the present invention to the above-mentioned range, the following method is preferred: using the plasticized polyvinyl alcohol acetal as described above in the filling bonding material of the present invention, and on this basis adjusting the acetalization degree, hydroxyl group content, acetyl group content, average polymerization degree and molecular weight of the polyvinyl alcohol, or adjusting the content of the plasticizer, etc.
[0148] More specifically, for example, if the content of the plasticizer is increased or the compatibility with the polyvinyl acetal is improved, the storage modulus becomes smaller; if the content of the plasticizer is reduced or the compatibility with the polyvinyl acetal is reduced, the storage modulus becomes larger. In addition, by increasing the molecular weight of the polyvinyl acetal, the storage modulus also increases, and if the molecular weight is reduced, the storage modulus becomes smaller. In addition, if the glass transition temperature (Tg) is increased, the storage modulus becomes higher, and if Tg is lower than 20°C, the decrease in the storage modulus becomes larger.
[0149] The visible light transmittance of the light-transmitting portion of the filling bonding material of the present invention is preferably 80% or more. If the visible light transmittance is 80% or more, it is possible to prevent the transmittance at the thick portion from being reduced, thereby reducing the visual recognition of the display content of the optical device, or preventing the optical device from being insufficiently bright and feeling dark. The more preferred lower limit of the visible light transmittance of the light-transmitting portion is 85%, and the further preferred lower limit is 90%.
[0150] The haze of the light-transmitting portion of the filling bonding material of the present invention is preferably 1% or less. If the haze is 1% or less, it is possible to prevent the display content of the optical device from being blurred, or the visual recognition or clarity from being reduced. In addition, for the filling bonding material of the present invention, it is preferred that the visible light transmittance in the light-transmitting portion is 80% or more and the haze is 1% or less. The more preferred upper limit of the haze of the light-transmitting portion is 0.5%, and the further preferred upper limit is 0.3%.
[0151] Visible light transmittance and haze can be measured according to JIS R 3106: 1998 and JIS K 7136: 2000, respectively, using, for example, a spectrophotometer U4100 manufactured by Hitachi High Technology Co., Ltd. It should be noted that haze can be calculated from total light transmittance (Tt) and diffuse light transmittance (Td). Specifically, the value obtained by dividing the diffuse light transmittance (Td) by the total light transmittance (Tt) is calculated as haze (haze = Td / Tt).
[0152] In the filling bonding material of the present invention, the refractive index of the light-transmitting portion at 23° C. is preferably 1.40 or more and 1.60 or less.
[0153] By setting in this way, especially when the adherend is glass, the refractive index difference at the interface between the filling bonding material and the adherend can be reduced, so that the optical quality of the optical device is not significantly impaired. The refractive index of the light-transmitting portion at 23° C. is more preferably in the range of 1.45 to 1.55.
[0154] The refractive index value is a value at a measurement wavelength of 589 nm (sodium D line). The refractive index can be measured according to JIS K 7142 using, for example, an Abbe refractometer (eg, general-purpose Abbe refractometer ER-7MW, manufactured by Eruma Sales Co., Ltd.).
[0155] The refractive index can be adjusted by changing the material composition (weight percentage) constituting the filling bonding material. For example, when polyvinyl acetal is used as the main raw material of the filling bonding material, the refractive index can be adjusted by adding a plasticizer.
[0156] The average residual phase difference (Rave) of the above-mentioned transparent part of the filling bonding material of the present invention is preferably 20nm / mm or less. If the average residual phase difference is 20nm / mm or less, it is possible to prevent the reduction of the optical quality of the optical device (specifically, the occurrence of bright spots or black spots, color unevenness, etc.). The more preferred upper limit of the average residual phase difference of the above-mentioned transparent part is 10nm / mm, and the particularly preferred upper limit is 5nm / mm.
[0157] It should be noted that the residual phase difference (R1) refers to the ratio of the phase difference (R0) at a specific position of the filling bonding material to the thickness (D) at that position (R1 = R0 / D). The average residual phase difference (Rave) can be obtained by looking down at the target area (translucent part) from the optical axis direction and dividing it into 100 parts, and calculating the average value of the residual phase difference of each divided area. The phase difference (R0) can be measured using a PA-200 manufactured by Photonic Lattice, etc. with a wavelength of 520nm.
[0158] The in-plane standard deviation (s) of the phase difference of the above-mentioned transparent portion of the filling bonding material of the present invention is preferably less than 10. If the in-plane standard deviation of the phase difference is less than 10, it is possible to prevent the reduction of the optical quality of the optical device (specifically, the occurrence of bright spots or black spots, color unevenness, etc.). The more preferred upper limit of the in-plane standard deviation of the phase difference of the above-mentioned transparent portion is 5, and the particularly preferred upper limit is 3.
[0159] It should be noted that the in-plane standard deviation (s) of the phase difference can be obtained by looking down at the target area (translucent part) from the optical axis direction, dividing it into more than 50,000 points, and calculating the standard deviation of the phase difference (R0) of each divided area.
[0160] The average residual phase difference (Rave) and the in-plane standard deviation (s) of the phase difference can be adjusted by adjusting the molding temperature, molding pressure, and adjusting the fluidity during the molding of the filling bonding material. For example, the high fluidity of the resin at high temperature can reduce the residual phase difference and the in-plane standard deviation of the phase difference. In addition, by heating (annealing) the filled bonding material after molding in a mold of the same size and adjusting the heating time, the residual phase difference and the in-plane standard deviation of the phase difference can be reduced.
[0161] Regarding the method for manufacturing the filling bonding material of the present invention, there is no particular limitation as long as it is possible to manufacture a filling bonding material with unequal thicknesses, and examples thereof include injection molding, etc. Also included are: a method of pressing a sheet after making a sheet-like filling bonding material; a forming method of cutting a thick film of a sheet-like filling bonding material using a laser or a water jet, etc. Also included are: a method of pressing a mixed powder of compound raw materials, or a granular ...
[0162] In addition, it is also possible to form the structure by dividing it into several parts (blocks) as described above, and finally join them to form shapes of unequal thickness. As a method for joining the blocks to form shapes of unequal thickness, it is preferred to apply heat and pressure to each block while applying a liquid joining agent or impregnating each block with a liquid joining agent and maintaining the conditions for a certain period of time.
[0163] The application of the filling and bonding material of the present invention is not particularly limited, but it is suitably used for bonding members together and filling spaces between members in optical devices having various shapes not limited to flat surfaces.
[0164] Examples of the above-mentioned optical devices include: mobile information terminals (such as smart phones, tablet computers), display devices using image display panels such as LCD, EL, PDP (such as electronic paper, PDA, TV, game consoles), light-emitting devices (such as lighting, etc.), light-receiving devices (such as solar cells, image sensors, etc.), etc.
[0165] Examples of the space between members to be filled with the filling and bonding material of the present invention include space between a touch panel module and a surface protection panel, space between a touch panel module and a polarizing film, and space between a plurality of transparent conductive films constituting a touch panel.
[0166] The touch panel module is not particularly limited. For example, a touch panel module commonly used in display devices such as a touch panel having multiple layers such as an ITO film can be used. The configuration of the touch panel module is not particularly limited. For example, out-cell type, in-cell type, on-cell type, protective glass integrated type, guard plate integrated type, etc. The mode of the touch panel module is also not particularly limited. For example, resistive film type, capacitive type, optical type, ultrasonic type, etc. can be mentioned.
[0167] The surface protection panel is not particularly limited, and for example, a surface protection panel commonly used in optical devices or display devices, such as a glass plate, a polycarbonate plate, and an acrylic plate, can be used.
[0168] The filling bonding material of the present invention can be directly bonded to the adherend when it is composed of a material having self-adhesive properties. In addition, even if the filling bonding material of the present invention does not have adhesiveness or bonding properties at room temperature, it can be bonded to the adherend by being heated to a temperature above the glass transition temperature (Tg). For example, the adherend can be bonded to the filling bonding material by using a heated vacuum laminator or an autoclave to appropriately adjust the heating temperature, pressure and processing time.
[0169] The filling bonding material of the present invention can be colored, for example, black, depending on the application, but is preferably a transparent filling bonding material. By being a transparent filling bonding material, the filling bonding material can also be suitably used in applications requiring high transparency such as optical devices. In addition, the transparent filling bonding material can be colorless and transparent, or highly transparent and colored (colored and transparent). As the above-mentioned colored and transparent, for example, blue transparent can be cited.
[0170] In addition, the filling and bonding material of the present invention may be colored only partially, or may have both a colorless transparent portion and a colored portion (a colored transparent portion).
[0171] By making the filling bonding material of the present invention colored and transparent, it is possible to improve the design of the device or adjust the color tone of light that passes through the filling bonding material.
[0172] In the case where the filling bonding material of the present invention is colored and transparent, the visible light transmittance is not particularly limited, but is preferably 85% or less. If the above-mentioned visible light transmittance is 85% or less, the color tone of the light passing through the filling bonding material can be adjusted while visually recognizing the coloring. The above-mentioned visible light transmittance is more preferably 60% or less. The lower limit of the above-mentioned visible light transmittance is not particularly limited, but is preferably 1% or more.
[0173] The filling bonding material of the present invention preferably has a light shielding portion or a light scattering portion in at least a portion.
[0174] Since the filling and bonding material of the present invention has the light-shielding portion or the light-scattering portion, shielding can be performed by the light-shielding portion or the light-scattering portion.
[0175] In the past, for example, on the back side of the above-mentioned surface protection panel, there is a case where a printed portion is formed on the peripheral portion for the purpose of shielding or the like. More specifically, when the above-mentioned touch panel module is bonded to the above-mentioned surface protection panel, there is a case where a printed portion is formed on the back side of the above-mentioned surface protection panel in order to shield the frame provided on the peripheral portion of the above-mentioned touch panel module. However, when a curved glass plate is used as the above-mentioned surface protection panel, a high temperature is required to bend the glass plate. Therefore, on the one hand, it is impossible to bend the flat glass after decorative printing is performed, and on the other hand, it is very difficult to perform decorative printing on the curved glass plate. By making the filling bonding material of the present invention have the above-mentioned shading portion or the above-mentioned light scattering portion, even if the printing portion is not provided on the back side of the above-mentioned surface protection panel, it can be shielded by the above-mentioned shading portion or the above-mentioned light scattering portion of the filling bonding material of the present invention.
[0176] Furthermore, by providing the filling and bonding material of the present invention with the light shielding portion or the light scattering portion, it is possible to improve the design property, suppress the deterioration of visibility due to light leakage or reflected light of the optical device, or make defects less noticeable.
[0177] The visible light transmittance of the shading portion is preferably 10% or less. If the visible light transmittance is 10% or less, light is appropriately blocked by the shading portion, shielding becomes easier, and the design can be improved, or the visual recognition of the optical device caused by light leakage and reflected light can be suppressed, or defects can be made less noticeable. The visible light transmittance is more preferably 5% or less, and further preferably 1% or less.
[0178] The lower limit of the visible light transmittance of the light-shielding portion is not particularly limited, but is preferably 0.01% or more.
[0179] The haze of the light scattering part is preferably 10% or more. If the haze is 10% or more, light is appropriately scattered by the light scattering part, shielding becomes easy, and the design can be improved or defects can be made less noticeable. The haze is more preferably 15% or more.
[0180] The method for adjusting the haze of the light scattering portion to the above range is not particularly limited, but specifically, for example, if calcium carbonate particles are added to the filling bonding material to scatter visible light, the visible light transmittance is high, the haze becomes high, and a shielding effect can be obtained.
[0181] The filling and bonding material of the present invention preferably further has a transparent portion when it has the light shielding portion or the light scattering portion. The transparent portion may be a colorless transparent portion or a colored portion (a colored transparent portion).
[0182] It should be noted that the visible light transmittance of the filling bonding material can be measured in accordance with JIS R3106: 1998. Specifically, for example, the filling bonding material as a sample for measurement can be pressed into a film with a thickness of 200 μm, laminated between two sheets of white glass (S9112: manufactured by Matsunami Glass Co., Ltd.), and the visible light transmittance can be measured using U4100 (manufactured by Hitachi High Technology Co., Ltd.).
[0183] The haze of the filling bonding material can be measured according to JIS K 7136: 2000 (ISO 14782: 1999). Specifically, for example, the filling bonding material as a sample for measurement can be pressed into a film with a thickness of 200 μm, laminated between two sheets of white glass (S9112: manufactured by Matsunami Glass Co., Ltd.), and the haze can be measured using NDH4000 (manufactured by Nippon Denshoku Industries Co., Ltd.).
[0184] The light shielding part and the light scattering part are preferably adjusted to transmit ultraviolet rays by adjusting the ultraviolet transmittance. If ultraviolet rays can be transmitted, the shielding properties of the light shielding part and the light scattering part can be improved while the light curing of the filling bonding material is not hindered.
[0185] The above-mentioned shading portion and the above-mentioned light scattering portion can be arranged on at least a part of the filling bonding material of the present invention, and the arrangement position thereof is not particularly limited. Among them, the above-mentioned shading portion and the above-mentioned light scattering portion are preferably arranged on the peripheral portion of the filling bonding material of the present invention. By arranging the above-mentioned shading portion or the above-mentioned light scattering portion on the peripheral portion of the filling bonding material of the present invention, for example, when the above-mentioned touch panel module is bonded to the above-mentioned surface protection panel, even if the printing portion is not provided on the back side of the above-mentioned surface protection panel, the frame provided on the peripheral portion of the above-mentioned touch panel module can be shielded. The above-mentioned shading portion can also be arranged on the end face of the filling bonding material of the present invention.
[0186] The shading portion and the light scattering portion may also be arranged in the central portion of the filling bonding material of the present invention. By arranging the shading portion or the light scattering portion in the central portion of the filling bonding material of the present invention, for example, the shading portion or the light scattering portion can be used as a "partition" of the display screen.
[0187] When the light shielding portion and the light scattering portion contain the polyvinyl acetal, the average degree of polymerization of the polyvinyl alcohol may be different from that of other portions, and the degree of crosslinking of the light shielding portion or the light scattering portion may also be different from that of other portions. In particular, when the light shielding portion or the light scattering portion is arranged at the peripheral portion of the filling bonding material, the heat resistance of the device can be improved by making the average degree of polymerization or the degree of crosslinking of the polyvinyl alcohol of the light shielding portion or the light scattering portion higher than that of other portions.
[0188] The coloring part, the light shielding part and the light scattering part may each have a monotonous color, or may have a color with a gradient, or may have a pattern such as a dot pattern. By making the coloring part, the light shielding part or the light scattering part have a color with a gradient, a dot pattern or the like, the design property can be further improved.
[0189] There is no particular limitation on the method for adjusting the visible light transmittance, haze, ultraviolet transmittance and color of the colored portion, the light shielding portion and the light scattering portion, and for example, a method of making them contain dyes or pigments can be cited. The dyes or pigments are not particularly limited, and examples of pigments include: inorganic pigments such as carbon black, titanium oxide, and calcium carbonate, nitro pigments, nitroso pigments, azo pigments, phthalocyanine pigments, etc. In addition, examples of dyes include: azo dyes, anthraquinone dyes, phthalocyanine dyes, etc. These dyes or pigments can be used alone or in combination of two or more.
[0190] The content of the dye or pigment is not particularly limited and can be appropriately adjusted according to the intended use.
[0191] When the filling and bonding material of the present invention has the above-mentioned colored portion, the above-mentioned light shielding portion or the light scattering portion, as a method for manufacturing the filling and bonding material of the present invention, a method of double-color injection molding using different materials can be cited. Another method can be cited: a block having a light shielding portion or a light scattering portion and a block not having a light shielding portion or a light scattering portion are respectively molded, and then they are finally joined.
[0192] Figure 6 This is a cross-sectional view schematically showing an example of the filling bonding material of the present invention and an example of its use form.
[0193] Figure 6 In (a), the filling bonding material 1 of the present invention fills the space between the flat touch panel module 2 and the curved surface protection panel 3 while bonding the two components. It should be noted that the shape of the filling bonding material 1 of the present invention is processed to follow the height difference of the frame 21 provided at the peripheral portion of the touch panel module 2.
[0194] Figure 6In (b), the filling bonding material 1 of the present invention has a light shielding portion 11 at the peripheral portion. The light shielding portion 11 can shield the frame 21 of the touch panel module 2 even if a printed portion is not provided on the back side of the surface protection panel 3 .
[0195] Figure 7 This is a perspective view schematically showing an example of the filling bonding material of the present invention having a light shielding portion.
[0196] Figure 7 The filling bonding material 1 of the present invention shown in (a) and (c) has a shape having a flat surface and a convex curved surface (convex lens shape) opposite to the flat surface, and has a light shielding portion 11 at the peripheral edge.
[0197] Figure 7 The filling bonding material 1 of the present invention shown in (b) has a shape having a flat surface and a convex curved surface opposite to the flat surface (convex lens shape), and has a light shielding portion 11 not only in the peripheral portion but also in the central portion.
[0198] Figure 7 The filling bonding material 1 of the present invention shown in (d) and (e) is a hemisphere (ellipse) and has a light shielding portion 11 at the peripheral edge.
[0199] A filling bonding material with a protective sheet comprising the filling bonding material of the present invention and a protective sheet covering the filling bonding material of the present invention is also one of the present invention. By setting such a structure, it is possible to prevent foreign matter from being mixed in from the time of production to the time of use.
[0200] The protective sheet is not particularly limited, but when the filling bonding material of the present invention contains the polyvinyl acetal, a polyolefin resin, for example, can be used as the material of the protective sheet.
[0201] In the filling bonding material with a protective sheet of the present invention, the 180° peel strength between the filling bonding material of the present invention and the protective sheet at 25° C. is preferably 3 N / 25 mm or less, more preferably 1 N / 25 mm or less.
[0202] As a method for producing the filling bonding material with a protective sheet of the present invention, for example, there is a method of performing two-color injection molding using different materials.
[0203] Figure 8 This is a perspective view schematically showing an example of the filling bonding material with a protective sheet of the present invention.
[0204] like Figure 8 As shown in FIG. 1 , the filling bonding material with a protective sheet 6 of the present invention comprises the filling bonding material 1 of the present invention and a protective sheet 5 covering the filling bonding material 1 of the present invention.
[0205] A laminated body comprising a pair of members to be joined (adherends) and the filling joining material of the present invention, wherein a space between the pair of members to be joined is filled with the filling joining material of the present invention, is also one of the present invention.
[0206] The above-mentioned joined member can be a member with a curved surface, and the filling joining material of the present invention is preferably set to an uneven thickness shape along the surface shape of the above-mentioned joined member. By configuring in this way, compared with the case where stress is applied to the joined member of a planar shape for joining, the stress applied to the joined member is reduced, thereby suppressing the degradation of the optical quality caused by strain.
[0207] The present invention also includes an optical device comprising the laminate of the present invention, at least one of a pair of joined members being a transparent member, and a refractive index difference between the transparent member and the filling and joining material of the present invention being 0.03 or less.
[0208] As the transparent member, for example, the above-mentioned surface protection panel etc. can be mentioned.
[0209] By making the refractive index difference between the transparent member and the filling bonding material of the present invention within the above range, light loss and image shift at the interface with the refractive index difference can be suppressed, and even if a member with a curved shape is used, the optical quality of the device can be satisfied. The above refractive index difference is more preferably 0.02 or less.
[0210] The refractive index difference between the transparent member and the filling bonding material can be determined using an Abbe refractometer (eg, General Abbe Refractometer ER-7MW, Eruma Sales Co., Ltd.) at a measurement wavelength of 589 nm (sodium D line) and a measurement temperature of 20°C.
[0211] The filling bonding material of the present invention can be used for a protective panel for an optical device.
[0212] The optical device protection panel may be a protective panel for an optical device as follows: a protective panel for an optical device having a first panel, a second panel, and the filling and bonding material of the present invention, wherein at least one of the first panel or the second panel has a curved surface, and the first panel and the second panel are directly bonded by the filling and bonding material of the present invention. Such a protective panel for an optical device is also one of the present invention.
[0213] By using such a protective panel for optical devices, it is possible to manufacture optical devices having various shapes not limited to flat surfaces using conventional flat display modules and touch panel modules. In addition, by using such a protective panel for optical devices, it is easier to handle and attach, for example, than when using a protective panel for a large curved glass surface.
[0214] At least one of the first panel and the second panel has a curved surface. As a panel with a curved surface, for example, a curved panel can be cited. Preferably, one of the first panel and the second panel has a curved surface and the other has a flat surface. By configuring in this way, even when a conventional display module or touch panel module that is generally in a flat shape is used, an optical device whose outermost surface is in a curved shape can be easily obtained. For example, a conventional adhesive or the like can be used to adhere the flat portion of the panel with a flat surface in the first panel and the second panel to an adherend (display module, touch panel module) with a flat shape. The first panel and the second panel can also both have curved surfaces.
[0215] The materials of the first panel and the second panel are not particularly limited, and the first panel and the second panel may be of the same material or of different materials. Specifically, for example, a glass plate, a polycarbonate plate, an acrylic plate, etc. may be used as a surface protection panel and are generally used for panels of optical devices or display devices. In addition, a touch panel module may be attached to these surface protection panels. Preferably, at least one of the first panel or the second panel is a glass plate. Alternatively, both the first panel and the second panel may be glass plates.
[0216] In the protective panel for an optical device of the present invention, the refractive index difference between the first panel or the second panel having a curved surface and the filling bonding material of the present invention is preferably 0.1 or less.
[0217] By setting the refractive index difference within the above range, light loss and image shift at the interface with the refractive index difference can be suppressed, and even when a panel with a curved surface is used, the optical quality of the device can be satisfied. The refractive index difference is more preferably 0.05 or less.
[0218] The refractive index can be determined using an Abbe refractometer (eg, General-purpose Abbe refractometer ER-7MW, manufactured by Eruma Sales Co., Ltd.) at a measurement wavelength of 589 nm (sodium D line) and a measurement temperature of 20°C.
[0219] In the protective panel for optical devices of the present invention, the storage modulus of the filling bonding material of the present invention at 23°C is preferably 1 MPa or more from the viewpoint of reprocessability. By setting the storage modulus at 23°C within the above range, the filling bonding material becomes less likely to be damaged when the protective panel for optical devices is reprocessed. The storage modulus at 23°C is more preferably 10 MPa or more, and further preferably 20 MPa or more.
[0220] In the protective panel for an optical device of the present invention, the filling bonding material of the present invention preferably has a tensile breaking strength of 1 MPa or more.
[0221] By setting the tensile strength at break to be within the above range, the filling and bonding material is less likely to be damaged when the optical device protection panel is reprocessed. The tensile strength at break is more preferably 5 MPa or more, and even more preferably 10 MPa or more.
[0222] The tensile strength at break can be determined, for example, by measuring a dumbbell-shaped test piece (No. 3) at 23° C. and 50% RH at a speed of 100 mm / min using a TENSILON universal testing machine manufactured by Orientec.
[0223] In the protective panel for an optical device of the present invention, the filling bonding material of the present invention preferably has a 180° peel strength of 5 N / 25 mm or more at 300 mm / min when the filling bonding material having a thickness of 200 μm is bonded to glass.
[0224] By setting the 180° peel strength within the above range, the filling bonding material is less likely to be damaged when the optical device protection panel is reprocessed. The 180° peel strength is more preferably 10 N / 25 mm or more, and further preferably 15 N / 25 mm or more.
[0225] The upper limit of the 180° peel strength is not particularly limited, but the preferred upper limit is 200N / 25mm. If the 180° peel strength exceeds 200N / 25mm, when the protective panel for optical devices is discarded, the strength is too high and it becomes difficult to separate into the first panel or the second panel and the filling bonding material, making it difficult to recycle. The more preferred upper limit of the 180° peel strength is 200N / 25mm.
[0226] The 180° peel strength can be determined, for example, by measuring a sheet-shaped filling bonding material having a thickness of 200 μm and a width of 25 mm bonded to an adherend at a tension rate of 300 mm / min at 23° C. and 50% RH using a TENSILON universal testing machine manufactured by Orientec.
[0227] Fig. 9 This is a diagram schematically showing an example of the protective panel for an optical device of the present invention.
[0228] At once Fig. 9In the protective panel 32 for optical devices shown in (a) (stereoscopic view) and (b) (sectional view), the first panel 31a and the second panel 31b are directly bonded by the filling bonding material 1. The filling bonding material 1 has a shape having a flat surface and a convex curved surface opposite to the flat surface (convex lens shape), and fills the space between the first panel 31a (having a curved surface) and the second panel 31b (flat shape) while bonding these components.
[0229] Fig.10 This is a diagram schematically showing an example of the protective panel for an optical device of the present invention.
[0230] At once Fig.10 In the protective panel 32 for optical devices shown in (a) (stereoscopic view) and (b) (sectional view), the first panel 31a and the second panel 31b are directly bonded by the filling bonding material 1. The filling bonding material 1 has a shape having a plane and a concave curved surface opposite to the plane (a concave lens shape), and fills the space between the first panel 31a (having a curved surface) and the second panel 31b (flat shape) while bonding them together.
[0231] Fig.11 This is a diagram schematically showing an example of the protective panel for an optical device of the present invention.
[0232] At once Fig.11 As for the protective panel 32 for optical devices shown in (a) (stereoscopic view) and (b) (sectional view), the first panel 31a and the second panel 31b are directly bonded by the filling bonding material 1. The filling bonding material 1 is a shape in which the curved surfaces are opposite to each other, and the first panel 31a (having a curved surface) and the second panel 31b (having a curved surface) are bonded together while filling these components. The curvatures of the relative curved surfaces of the filling bonding material 1 can be the same or different.
[0233] Fig.12 This is a diagram schematically showing an example of the protective panel for an optical device of the present invention.
[0234] At once Fig.12 As for the protective panel 32 for optical devices shown in the figure, the first panel 31a and the second panel 31b to which the touch panel module 2 is attached are directly bonded by the filling bonding material 1. Fig.12 As shown, the touch panel module 2 may be attached to the first panel 31 a.
[0235] Fig.13 This is a diagram schematically showing an example of the usage of the optical device protection panel of the present invention.
[0236] At once Fig.13As for the protective panel 32 for optical devices shown in the figure, the first panel 31a and the second panel 31b to which the touch panel module 2 is attached are directly bonded by the filling bonding material 1. Fig.13 As shown, the optical device protection panel 32 is used after being attached to the display module 9 by, for example, an adhesive or bonding agent 8. The optical device 7 is composed of the optical device protection panel 32 and the display module 9. It should be noted that the optical device protection panel 32 and the display module 9 may be fixed by mechanical methods such as fitting, screwing, etc. instead of the adhesive or bonding agent 8.
[0237] As a method for manufacturing the protective panel for optical devices of the present invention, for example, the following method can be cited. That is, the following method can be cited: the first panel and the second panel are formed into desired shapes in advance (for example, the first panel is formed into a panel with a curved surface, and the second panel is formed into a panel with a flat shape), and then the first panel, the filling bonding material of the present invention, and the second panel are stacked, and the stacked body is heat-treated using a heating vacuum laminator or an autoclave.
[0238] Another method of manufacturing the optical device protection panel of the present invention may include bending either the first panel or the second panel when directly bonding the first panel and the second panel using the filling bonding material of the present invention.
[0239] Fig.14 This is a diagram schematically showing an example of a method for producing a protective panel for an optical device according to the present invention.
[0240] like Fig.14 As shown, when the first panel 31 a (flat shape) and the second panel 31 b (flat shape) are directly bonded together using the filling bonding material 1 , the first panel 31 a may be bent.
[0241] Specifically, for example, a glass with a thickness of 200 μm serving as the first panel 31a (planar shape) is pressurized with a roller along the filling bonding material 1 so that it is bent and closely adheres to the filling bonding material 1, thereby enabling the first panel to be bent while directly bonding the first panel to the second panel with the filling bonding material of the present invention.
[0242] The use of the optical device protection panel of the present invention is not particularly limited, but it can be suitably used for optical devices having various shapes not limited to flat surfaces.
[0243] Examples of the above-mentioned optical devices include: mobile information terminals (such as smart phones, tablet computers), display devices using image display panels such as LCD, EL, PDP (such as electronic paper, PDA, TV, game consoles), light-emitting devices (such as lighting, etc.), light-receiving devices (such as solar cells, image sensors, etc.), etc.
[0244] The optical device protection panel of the present invention is used after being bonded to a display module or a touch panel module via an adhesive or a pressure-sensitive adhesive.
[0245] The touch panel module is not particularly limited. For example, a touch panel module commonly used in display devices such as a touch panel having multiple layers such as an ITO film can be used. The configuration of the touch panel module is not particularly limited. For example, out-cell type, in-cell type, on-cell type, protective glass integrated type, guard plate integrated type, etc. The mode of the touch panel module is also not particularly limited. For example, resistive film type, capacitive type, optical type, ultrasonic type, etc. can be mentioned.
[0246] Fig.15 and Fig.16 FIG. 2 is a diagram schematically showing an example of an optical device of the present invention. Fig.15 and Fig.16 As shown, as the optical device 7 of the present invention, there can be mentioned a vehicle-mounted panel having various shapes (curved shape, etc.) not limited to a flat surface.
[0247] Effects of the Invention
[0248] According to the present invention, a bonding material that can be suitably used for filling between components while bonding components in optical devices having various shapes not limited to planes can be provided. In addition, according to the present invention, a filling bonding material with a protective sheet, a laminate, an optical device, and a protective panel for an optical device containing the filling bonding material can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0249] Figure 1 This is a diagram schematically showing an example of the filling bonding material of the present invention and an example of its use form.
[0250] Figure 2 This is a diagram schematically showing an example of the filling bonding material of the present invention and an example of its use form.
[0251] Figure 3 This is a perspective view schematically showing an example of the filling bonding material of the present invention.
[0252] Figure 4 The following are a perspective view and a cross-sectional view schematically showing an example of the filling bonding material of the present invention.
[0253] Figure 5 This is a cross-sectional view schematically showing an example of the filling bonding material of the present invention and an example of its use form.
[0254] Figure 6 This is a cross-sectional view schematically showing an example of the filling bonding material of the present invention and an example of its use form.
[0255] Figure 7 This is a perspective view schematically showing an example of the filling bonding material of the present invention having a light shielding portion.
[0256] Figure 8 This is a perspective view schematically showing an example of the filling bonding material with a protective sheet of the present invention.
[0257] Fig. 9 This is a diagram schematically showing an example of the protective panel for an optical device of the present invention.
[0258] Fig.10 This is a diagram schematically showing an example of the protective panel for an optical device of the present invention.
[0259] Fig.11 This is a diagram schematically showing an example of the protective panel for an optical device of the present invention.
[0260] Fig.12 This is a diagram schematically showing an example of the protective panel for an optical device of the present invention.
[0261] Fig.13 This is a diagram schematically showing an example of the usage of the optical device protection panel of the present invention.
[0262] Fig.14 This is a diagram schematically showing an example of a method for producing a protective panel for an optical device according to the present invention.
[0263] Fig.15 This is a diagram schematically showing an example of an optical device having the filling bonding material of the present invention.
[0264] Fig.16 This is a diagram schematically showing an example of an optical device having the filling bonding material of the present invention.
[0265] Fig.17 A schematic diagram illustrating the arc length and chord length of a surface.
[0266] Explanation of symbols
[0267] 1Filling joint material
[0268] 11 light shielding part
[0269] 2Touch panel module
[0270] 21 Frame
[0271] 3 Surface protection panel
[0272] 31a First panel
[0273] 31b Second panel
[0274] 32 Protective panel for optical devices
[0275] 4 Hollow
[0276] 5. Protective sheet
[0277] 6Filling joint material with protective sheet
[0278] 7. Optics
[0279] 8 Adhesive or adhesive
[0280] 9 Display Module DETAILED DESCRIPTION
[0281] The present invention will be described in more detail below with reference to Examples, but the present invention is not limited to these Examples.
[0282] (Preparation of polyvinyl butyral 1 (PVB1))
[0283] In a reactor equipped with a stirring device, 2700 mL of ion exchange water, 300 g of polyvinyl alcohol having an average degree of polymerization of 850 and a saponification degree of 99.0 mol% were added, and heated and dissolved while stirring to obtain a solution. Next, 35 wt% hydrochloric acid was added as a catalyst to a hydrochloric acid concentration of 0.2 wt%, and after adjusting the temperature to 15°C, 21 g of n-butyraldehyde (n-BA) was added while stirring. Then, when 145 g of n-butyraldehyde (n-BA) was added, white granular polyvinyl butyral was precipitated. 15 minutes after precipitation, 35 wt% hydrochloric acid was added to a hydrochloric acid concentration of 1.8 wt%, and heated to 50°C and aged at 50°C for 2 hours. Next, after the solution was cooled and neutralized, the polyvinyl butyral was washed with water and dried to obtain polyvinyl butyral (PVB1). The obtained polyvinyl butyral 1 (PVB1) had a hydroxyl group content of 31.0 mol%, an acetyl group content of 1.0 mol%, and a butyralization degree of 68.0 mol%.
[0284] (Preparation of polyvinyl butyral 2 (PVB2))
[0285] In a reactor equipped with a stirring device, 2700 mL of ion exchange water, 300 g of polyvinyl alcohol with an average degree of polymerization of 850 and a saponification degree of 88.0 mol% were added, and heated and dissolved while stirring to obtain a solution. Then, 35 wt% hydrochloric acid was added as a catalyst to a hydrochloric acid concentration of 0.6 wt%, and after adjusting the temperature to 15°C, 14 g of n-butyraldehyde (n-BA) was added while stirring. Then, when 186 g of n-butyraldehyde (n-BA) was added, white granular polyvinyl butyral was precipitated. 15 minutes after precipitation, 35 wt% hydrochloric acid was added to a hydrochloric acid concentration of 3.9 wt%, heated to 45°C and aged at 45°C for 3 hours. Then, after the solution was cooled and neutralized, the polyvinyl butyral was washed with water and dried to obtain polyvinyl butyral 2 (PVB2). The obtained polyvinyl butyral 2 (PVB2) had a hydroxyl group content of 24.0 mol%, an acetyl group content of 12.0 mol%, and a butyralization degree of 64.0 mol%.
[0286] (Example 1)
[0287] (1) Manufacturing of filling and bonding materials
[0288] A mixture of 20 parts by weight of triethylene glycol-di-2-ethylhexanoate (3GO) as a plasticizer and 100 parts by weight of polyvinyl butyral 1 (PVB1) prepared in (1) above was heated and pressed to obtain a filling bonding material (with a principal curvature of 1 / 1000 mm) having an unequal thickness shape (a shape having a flat surface and a convex curved surface opposite to the flat surface) -1 , chord length 200mm, maximum thickness (t1) 5.2mm, minimum thickness 200μm, maximum width 200mm).
[0289] (2) Determination of the storage modulus of the filling bonding material at 20°C and 80°C, and determination of Tg (maximum value of tan δ)
[0290] The viscoelasticity of the filling and bonding material was measured by a dynamic viscoelasticity measuring device (ARES-G2 manufactured by TA INSTRUMENTS) under the conditions of heating from -50°C to 100°C at a heating rate of 3°C / min, a frequency of 1 Hz, and a shear strain of 1%. The storage modulus of the filling and bonding material at 20°C and 80°C was determined. The results were 6.9×10 7 Pa and 9.2×10 5 Pa. In addition, Tg is 29.3°C.
[0291] (3) Determination of visible light transmittance and haze
[0292] The visible light transmittance and haze of the light-transmitting portion of the filling bonding material were measured using a spectrophotometer U4100 manufactured by Hitachi High Technology Co., Ltd. in accordance with JIS K 7136:2000.
[0293] (4) Determination of the average residual phase difference (Rave)
[0294] The transparent part of the filling bonding material is viewed from the optical axis direction, divided into 100 parts, and the phase difference (R0) of each divided area is measured using the PA-200 manufactured by Photonic Lattice with a wavelength of 520nm. The thickness value (D) of the filling bonding material at the position of each area is used to calculate the average value of the residual phase difference (R1 = R0 / D) as Rave.
[0295] (5) Measurement of in-plane standard deviation of phase difference (s)
[0296] The light-transmitting area filled with the bonding material was viewed from the optical axis direction and divided into 50,000 points. The phase difference of each divided area was measured using a PA-200 manufactured by Photonic Lattice with a wavelength of 520 nm. The measurement results were processed using software (PA-View 2.2.4) to obtain the in-plane standard deviation (s) of the phase difference.
[0297] (Example 2)
[0298] The filled bonding material obtained in Example 1 was placed in a mold of the same size and subjected to an annealing treatment (60° C., 5 hours).
[0299] (Example 3)
[0300] A filled bonding material was obtained in the same manner as in Example 2 except that the blending amount of the plasticizer was changed to 30 parts by weight.
[0301] (Example 4)
[0302] A filled bonding material was obtained in the same manner as in Example 2 except that PVB2 was used instead of PVB1 and the amount of the plasticizer was changed to 60 parts by weight.
[0303] (Example 5)
[0304] A filled bonding material was obtained in the same manner as in Example 4 except that the blending amount of the plasticizer was changed to 25 parts by weight.
[0305] (Example 6)
[0306] A filling bonding material was obtained in the same manner as in Example 1 except that a cobalt blue pigment (CI Pigment Blue 28 manufactured by Asahi Kasei Industries) was added to the plasticizer. 0.02 parts by weight of the cobalt blue pigment was added based on 1100 parts by weight of PVB.
[0307] (Example 7)
[0308] A filling bonding material was obtained in the same manner as in Example 1 except that a cobalt blue pigment (manufactured by Sealy Chemicals, Inc., Nanotech Cobalt Blue Paste (15% alcohol solution)) was added to the plasticizer. 0.012 parts by weight of the cobalt blue pigment (solid content) was added to 100 parts by weight of PVB1.
[0309] (Example 8)
[0310] A filling bonding material was obtained in the same manner as in Example 7 except that the amount of cobalt blue pigment (solid content) added was 0.0072 parts by weight relative to 100 parts by weight of PVB1.
[0311] (Example 9)
[0312] A filling bonding material was obtained in the same manner as in Example 2 except that the annealing temperature was changed to 40°C.
[0313] (Example 10)
[0314] A filled bonding material was obtained in the same manner as in Example 1 except that no plasticizer was added.
[0315] (evaluate)
[0316] The filling and bonding materials obtained in Examples 1 to 9 were evaluated by the following method. The results are shown in Table 1.
[0317] (1) Evaluation of filling and bonding properties between components
[0318] Two sheets of flat glass of 200 mm × 100 mm and 1 mm thickness were prepared. One sheet was used directly as a flat sheet, and the other sheet was heat-formed and bent along the 200 mm side to produce curved glass with a curvature radius of 1000 mm.
[0319] Next, the flat glass, the filling bonding material, and the curved glass are stacked in this order by placing the flat glass, the filling bonding material, and the curved glass so that the curved surface shape of the filling bonding material corresponds to that of the flat glass.
[0320] Then, the laminate was treated at 70°C and 200 Pa for 3 minutes using a heated vacuum laminator. Further, it was treated at 70°C and 5 MPa for 30 minutes using an autoclave to produce a laminate of flat glass, filled bonding material, and bent glass (a protective panel for an optical device in which the flat glass and the bent glass are directly bonded through the filled bonding material). The obtained laminate was visually observed immediately after production (initially) and 48 hours later to confirm the presence of residual space or foaming due to poor bonding. A case without residual space or foaming was evaluated as ○, and a case with residual space or foaming was evaluated as ×.
[0321] (2) Evaluation of high-temperature reliability
[0322] The laminate (protective panel for an optical device in which the flat glass and the bent glass are directly bonded through the filled bonding material) obtained in the same manner as in (1) above was left standing in a high-temperature and high-humidity environment of 85°C and 85% for 240 hours, and the presence or absence of foaming was visually confirmed. A case without foaming was evaluated as ○, and a case with foaming was evaluated as ×.
[0323] (3) Evaluation of optical quality
[0324] Characters with a black background and white gaps (in Japanese: 白抜き) were displayed on a flat panel display, and the black display part of the background was observed while wearing polarized glasses. Then, the laminate (protective panel for an optical device in which the flat glass and the bent glass are directly bonded through the filled bonding material) obtained in the same manner as in (1) above was placed on the display surface of the flat panel display, and the presence or absence of white parts (white gaps) and the presence or absence of blurred characters were visually observed.
[0325] The results before and after placing the laminate on the flat panel display were compared. Regarding the presence or absence of white parts (white gaps), for the black display part, a case where it remained black as it was without any confirmed color change was evaluated as ○, a case where it could not be recognized as white but had a strange feeling was evaluated as △, and a case where a white part was clearly visually confirmed was evaluated as ×. Similarly, regarding the presence or absence of blurred characters, a case where the ends of the characters could be clearly recognized was evaluated as ○, a case where the ends of the characters were recognized as skewed was evaluated as △, and a case where the shape of the characters was significantly deformed, unclear, and blurred was evaluated as ×.
[0326] [Table 1]
[0327]
[0328] Industrial applicability
[0329] According to the present invention, a bonding material that can be suitably used for filling between components while bonding components in optical devices having various shapes not limited to planes can be provided. In addition, according to the present invention, a filling bonding material with a protective sheet, a laminate, an optical device, and a protective panel for an optical device containing the filling bonding material can be provided.
Claims
1. A filling and bonding material, characterized in that: Has a shape of unequal thickness.
2. The filling and bonding material according to claim 1, characterized in that: The maximum value t1 of the thickness is 500 μm or more.
3. The filling and bonding material according to claim 1 or 2, characterized in that: The maximum width is 50 mm or more.
4. The filling and bonding material according to any one of claims 1 to 3, characterized in that The main curvature is 1 / 5000mm -1 The above surface.
5. The filling and bonding material according to claim 4, characterized in that: The chord length of the curved surface is 50 mm or more.
6. The filling and bonding material according to claim 4 or 5, characterized in that: The Gaussian curvature of a surface can be positive or negative.
7. The filling and bonding material according to any one of claims 1 to 6, characterized in that Has at least one plane.
8. The filling and bonding material according to claim 7, characterized in that: It has a flat surface and a curved surface opposite to the flat surface.
9. The filling and bonding material according to any one of claims 1 to 8, characterized in that Having a light-transmitting portion, In the light-transmitting portion, visible light transmittance is 80% or more and haze is 1% or less.
10. The filling and bonding material according to any one of claims 1 to 9, characterized in that Having a light-transmitting portion, The average residual phase difference Rave of the light-transmitting portion is less than or equal to 20 nm / mm.
11. The filling and bonding material according to any one of claims 1 to 10, characterized in that Having a light-transmitting portion, The in-plane standard deviation s of the phase difference of the light-transmitting portion is 10 or less.
12. The filling bonding material according to any one of claims 1 to 11, characterized in that The glass transition temperature Tg is 10° C. or higher and 60° C. or lower.
13. The filling and bonding material according to any one of claims 1 to 12, characterized in that Contains polyvinyl acetal at least on the surface.
14. The filling and bonding material according to any one of claims 1 to 13, characterized in that A light shielding portion is provided at least in a portion.
15. The filling and bonding material according to claim 14, characterized in that The visible light transmittance of the light shielding portion is 10% or less.
16. The filling and bonding material according to any one of claims 1 to 13, characterized in that: A light scattering portion is provided at least in a portion.
17. The filling and bonding material according to claim 16, characterized in that The haze of the light scattering portion is 10% or more.
18. The filling and bonding material according to any one of claims 14 to 17, characterized in that: The light-shielding portion or the light-scattering portion contains a dye or a pigment.
19. The filling bonding material according to any one of claims 14 to 18, characterized in that The light shielding portion or the light scattering portion is arranged at the peripheral portion filled with the bonding material.
20. A filling joint material with a protective sheet, characterized in that: have: A filling bonding material according to any one of claims 1 to 19, and a protective sheet covering the filling bonding material.
21. A laminated body, characterized in that: A method of manufacturing a bonding apparatus comprising a pair of bonding members and a filling bonding material according to any one of claims 1 to 19, The space between the pair of joined members is filled with the filling joining material.
22. An optical device, characterized in that: A laminate according to claim 21, At least one of the pair of joined members is a transparent member, The difference in refractive index between the transparent member and the filling bonding material is 0.03 or less.
23. A protective panel for an optical device, characterized in that: A first panel, a second panel, and a filling bonding material having a shape of unequal thickness, At least one of the first panel or the second panel has a curved surface, The first panel and the second panel are directly bonded via the filling bonding material.
24. The protective panel for an optical device according to claim 23, characterized in that: The difference in refractive index between the first panel or the second panel having a curved surface and the filling bonding material is 0.1 or less.
25. The protective panel for an optical device according to claim 23 or 24, characterized in that: At least one of the first panel or the second panel is a glass panel.
26. An optical device, characterized in that: A protective panel for an optical device according to any one of claims 23 to 25.
Citation Information
Patent Citations
Transparent adhesive sheet and image display device including the same
JP2011074308A